Biodegradable microbeads with enhanced optical effects

The shortcomings of existing beads in environmental degradation and optical properties are solved by developing biodegradable particles containing mixed cellulose esters of specific substitution ranges, achieving a combination of efficient degradation and good optical properties.

CN119604541APending Publication Date: 2025-03-11EASTMAN CHEM CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480003485.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-22
Filing Date
2024-03-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing microbeads are mainly made of plastics or polymers, which have problems such as limited biodegradability and difficulty in capturing by water treatment facilities, resulting in environmental pollution. At the same time, consumers have high requirements for the optical properties of personal care products and cosmetics.

Method used

Biodegradable microparticles containing mixed cellulose esters are developed that achieve at least 50% biodegradability within 60 days and have a haze transmittance of at least 10%. The degree of substitution of mixed cellulose ester is: acetyl substituent 0.1-2.3, propionyl or butyryl group 0.1-1.5, and hydroxyl substituent 0.6-2.8.

Benefits of technology

The biodegradable microbeads are realized, which can be effectively degraded in water treatment facilities and have good optical properties to meet consumers' expectations for personal care products and cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253623000000081
    Figure BDA0005253623000000081
  • Figure BDA0005253623000000621
    Figure BDA0005253623000000621
  • Figure BDA0005253623000000641
    Figure BDA0005253623000000641
Patent Text Reader

Abstract

Provided is a biodegradable microbead exhibiting an excellent optical effect. More specifically, provided are biodegradable microparticles formed from biodegradable mixed cellulose esters that exhibit excellent optical effects, such as haze transmittance, which are very beneficial when used in the production of cosmetic formulations. The microbeads produced also exhibit enhanced robustness, sphericity, and smoothness.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Microbeads are particles with a diameter of less than 1 millimeter (mm). These particles are sometimes contained in consumer products, such as personal care products and cosmetics. Many of these products containing microbeads are designed to be applied and then washed or rinsed from the user's body. When the product containing microbeads is washed or rinsed from the user's body, the particles are washed into the sewer and received at the municipal water treatment facility. In the past, many known microbeads were formed by plastic or polymer materials, such as polyethylene, polypropylene, polymethyl methacrylate, nylon, polyurethane, etc. These materials usually have limited biodegradability. In addition, the small size of the particles limits their ability to be captured at water treatment facilities, so that the particles may be discharged from the facilities and enter larger water bodies (e.g., rivers, oceans and seas). Once in these larger water bodies, plastic or polymer microbeads may be swallowed by wild animals or cause other environmental problems. Therefore, people are exploring the possibility of producing microbead particles using more environmentally friendly materials recently. However, consumers often have high expectations for the personal care products and / or cosmetics (including products containing microbeads) used. For example, consumers expect these personal care and cosmetic products to exhibit certain optical properties that enable the product to blend with natural skin tone and easily hide any undesirable imperfections.

[0002] Therefore, there is a need to develop biodegradable microbeads that meet environmental and consumer expectations, particularly with respect to optical properties for use in personal care products and cosmetics. Summary of the invention

[0003] In one aspect, the present technology relates to biodegradable microparticles comprising mixed cellulose esters, wherein the biodegradable microparticles exhibit at least 50% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods, and exhibit a haze transmittance of at least 10%. In addition, the mixed cellulose esters comprise: (a) an average degree of substitution (“DS”) of acetyl substituents in the range of 0.1 to 2.3; Ac ”), (b) an average degree of substitution (“DS Pr ”) or the average degree of substitution of butyryl substituents (“DS Bu ”), and (c) an average degree of substitution (“DS OH ”).

[0004] In one aspect, the present technology relates to biodegradable microparticles comprising mixed cellulose esters, wherein the biodegradable microparticles exhibit at least 50% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods, and exhibit a haze transmittance of at least 10%. In addition, the mixed cellulose esters comprise: (a) an average degree of substitution (“DS”) of acetyl substituents in the range of 0.1 to 2.3; Ac ”), (b) an average degree of substitution (“DS Bu ”), and (c) an average degree of substitution (“DS OH ”).

[0005] In one aspect, the present technology relates to a method for forming biodegradable microparticles. Generally, the method comprises: (a) forming a coating comprising a mixed cellulose ester; (b) contacting at least a portion of the coating with an aqueous mixture under agitation to thereby form an initial emulsion; (c) converting at least a portion of the initial emulsion into a dispersion comprising a solid phase and a liquid phase, wherein the solid phase comprises biodegradable microparticles; and (d) recovering at least a portion of the biodegradable microparticles from the dispersion. The biodegradable microparticles exhibit at least 50% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods, and exhibit a haze transmittance of at least 10%. In addition, the mixed cellulose ester comprises: (a) an average degree of substitution ("DS) of acetyl substituents in the range of 0.1 to 2.3; Ac ”), (b) an average degree of substitution (“DS Pr ”) or the average degree of substitution of butyryl substituents (“DS Bu ”), and (c) an average degree of substitution (“DS OH ”). BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 is a schematic diagram of an exemplary method for making cellulose ester microbeads.

[0008] Figure 2 is a more detailed schematic diagram of an example method for making cellulose ester microbeads.

[0009] Figure 3 is a schematic diagram of an alternative process for making cellulose ester microbeads by continuous particle formation.

[0010] Figure 4Schematic representation of alternative methods for making cellulose ester microspheres by separate coating and aqueous mixture formation and combined emulsion / dispersion formation and particle hardening.

[0011] Figure 5 is a schematic diagram of an alternative method for making cellulose ester microbeads by combined emulsion / dispersion formation.

[0012] Figure 6 is a schematic diagram of an alternative process for making cellulose ester microbeads by combined emulsion / dispersion formation and particle hardening.

[0013] Figure 7 is a schematic diagram of an alternative method for making cellulose ester microbeads by flash evaporation of the solvent prior to hardening of the particles. DETAILED DESCRIPTION

[0014] The present disclosure relates to compositions and methods for making hardened or jet-milled cellulose ester (CE) microbeads that exhibit excellent optical properties. The methods disclosed herein enable the robustness of the microbeads produced to be controlled so that they exhibit desired tactile and optical qualities. For example, the CE microbeads may have enhanced robustness, sphericity and smoothness, low moisture content and / or low free acid content. These qualities, together with the biodegradability of CE, make the CE microbeads produced herein very suitable for use in personal care products, cosmetics, and the like.

[0015] The present invention can be more easily understood by reference to the following detailed description and examples provided herein. It should be understood that the disclosure is not limited to the specific methods, preparations and conditions described, as these may vary. It should also be understood that the terms used herein are only for the purpose of describing specific aspects of the disclosed embodiments and are not intended to be limiting.

[0016] Values ​​may be expressed as "about" or "approximately" a given numerical value. Similarly, ranges may be expressed herein as from "about" one particular value and / or to "about" or another particular value. When such a range is expressed, another aspect includes from one particular value and / or to another particular value. Similarly, when values ​​are expressed as approximate values, by use of the antecedent "about", it will be understood that the particular value forms another aspect.

[0017] As used herein, the terms "a", "an", and "the" mean one or more than one.

[0018] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as containing components A, B, and / or C, the composition may contain only A; only B; only C; a combination of A and B; a combination of A and C, a combination of B and C; or a combination of A, B, and C.

[0019] As used herein, the terms "comprising," "comprises," and "comprise" are open transition words that are used to transition from an object recited before the term to one or more elements recited after the term, wherein the one or more elements listed after the transition word are not necessarily the only elements that make up the subject matter.

[0020] As used herein, the terms "having, has, and have" have the same open-ended meaning as "comprising, comprises, and comprise" provided above.

[0021] As used herein, the terms "including, include, and included" have the same open-ended meaning as "comprising, comprise, and comprise" provided above.

[0022] As used herein, "mixed cellulose esters" shall mean cellulose esters having at least two different ester substituents on a single cellulose ester polymer chain.

[0023] "Degree of substitution" is used to describe the average substitution level of substituents per anhydroglucose unit ("AGU"). In general, conventional cellulose contains three hydroxyl groups that can be substituted in each AGU unit. Therefore, DS can have a value between 0 and 3. However, low molecular weight cellulose mixed esters may have a total degree of substitution slightly higher than 3 resulting from end group contributions. Low molecular weight cellulose mixed esters will be discussed in more detail later in this disclosure. Since DS is a statistical average, a value of 1 does not guarantee that each AGU has a substituent. In some cases, there may be unsubstituted anhydroglucose units, some with two substituents and some with three substituents, and generally, this value will be a non-integer. "Total DS" is defined as the average number of all substituents per anhydroglucose unit. The degree of substitution for each AGU can also refer to a specific substituent, such as, for example, a hydroxyl, acetyl, butyryl or propionyl. In addition, the degree of substitution can specify a specific hydroxyl group based on the carbon unit of the anhydroglucose unit.

[0024] "Spheroid" in terms of shape means that the average sphericity of the particles is less than 70%. "Spherical" in terms of shape means that the average sphericity of the particles is equal to or greater than 70%.

[0025] When the degree of substitution refers to the hydroxyl group, DS OH When calculating the total degree of substitution, the reference is to the average hydroxyl group of each anhydroglucose that is not substituted. Therefore, DS is not used in calculating the total degree of substitution. OH .

[0026] This specification uses numerical ranges to quantify certain parameters related to the present invention. It should be understood that when numerical ranges are provided, these ranges should be interpreted as providing literal support for claim limitations that only recite the lower limit of the range and claim limitations that only recite the upper limit of the range. For example, the disclosed numerical range of 10 to 100 provides literal support for claims that recite "greater than 10" (no upper limit) and claims that recite "less than 100" (no lower limit).

[0027] This specification uses specific values ​​to quantify certain parameters related to the present invention, wherein specific values ​​do not explicitly belong to a part of a numerical range. It should be understood that each specific concrete value provided herein should be interpreted as providing extensive, intermediate and narrow ranges of text support. The wide range associated with each specific value is 60% of this value (rounded to two significant figures) plus or minus this value. The medium range associated with each specific value is 30% of this value (rounded to two significant figures) plus or minus this value. The narrow range associated with each specific value is 15% of this value (rounded to two significant figures) plus or minus this value. For example, if a specific temperature of 62℉ is described in the specification, such a description provides text support for a wide range of values ​​from 25℉ to 99℉ (62℉+ / -37℉), a medium range of values ​​from 43℉ to 81℉ (62F+ / -19℉), and a narrow range of values ​​from 53℉ to 71℉ (62℉+ / -9℉). These broad, medium, and narrow ranges apply not only to the specific values, but also to the differences between those specific values. Thus, if the specification describes a first pressure of 110 psia and a second pressure of 48 psia (a difference of 62 psi), the broad, medium, and narrow ranges for the pressure difference between the two streams would be 25 to 99 psi, 43 to 81 psi, and 53 to 71 psi, respectively.

[0028] Throughout this application, where patents or publications are cited, the entire contents of these references are intended to be incorporated by reference into this application to the extent they are not inconsistent with the present invention, in order to more fully describe the state of the art to which this invention pertains.

[0029] Reference now Figure 1 , cellulose ester (CE) 100, solvent 102, water 104, hydrocolloid 106, and surfactant 108 can be combined in one or more units to make CE microbeads 112. In the illustrated example, CE 100, solvent 102, water 104, hydrocolloid 106, and surfactant 108 are combined at unit 110 to form an initial emulsion therein. The initial emulsion includes a dispersed phase and a continuous phase. The dispersed phase includes at least a portion of CE 100 and at least a portion of solvent 102. The continuous phase includes at least a portion of water 104, at least a portion of hydrocolloid 106, and at least a portion of surfactant 108.

[0030] Once the initial emulsions are combined, the initial emulsions can be agitated at unit 110 to form a pre-hardened dispersion comprising a solid phase and a liquid phase. The solid phase comprises initial microparticles comprising at least a portion of CE 100 and at least a portion of solvent 102. The liquid phase comprises at least a portion of water 104, at least a portion of hydrocolloid 106, and at least a portion of surfactant 108. Additional water 104 (i.e., drowning liquid / extractant) can be added to the pre-hardened dispersion to increase the water concentration around the initial microparticles. An initial hardened dispersion comprising the initial microparticles and drowning liquid is thereby formed. The initial hardened dispersion can be agitated at unit 110 to facilitate the transfer of solvent from the initial microparticles to the drowning liquid. The solvent transfer facilitates the hardening of the initial microparticles, thereby producing hardened CE microbeads 112, which are entrained in the drowning liquid filled with solvent.

[0031] The CE microbeads 112 may be recovered from the dispersion 114 by first being processed at a solid / liquid separation unit 116. A solid stream 118 containing the CE microbeads 112 may be directed to a solid processing unit 120 where the CE microbeads 112 are washed with water 122 and then dried to recover the CE microbeads 112, as will be described in more detail below. A liquid stream 124 formed from the flooding liquid filled with solvent may be directed to a liquid processing unit 126. Optionally, an excess liquid stream 128 directed from unit 110 and a wash water stream 130 from unit 120 may also be received at unit 126 for processing therein.

[0032] At unit 126, the liquid received therein may be separated into at least a water-rich stream 132 and a rich solvent stream 134. In some embodiments, the water-rich stream 132 may be recovered and at least a portion thereof used in unit 110. In addition, the rich solvent stream 134 may be recycled and used as at least a portion of the solvent used to form CE microbeads 112 in unit 110. Reuse of recovered water and / or solvent is advantageous for improving the economics of the CE microbead formation methods described herein.

[0033] Mixed cellulose esters

[0034] In one embodiment or in combination with any of the embodiments mentioned herein, CE 100 may be a mixed cellulose ester.

[0035] Typically, the cellulose esters described herein (such as CE 100) can be produced by any method known in the art. Examples of methods for producing cellulose esters are taught in Kirk-Othmer, Encyclopedia of Chemical Technology, 5th edition, volume 5, Wiley-Interscience, New York (2004), pages 394-444, the disclosure of which is incorporated herein by reference in its entirety. Cellulose is the starting material for producing cellulose esters and can be obtained in different grades and from sources such as, for example, lignocellulosic sources (e.g., softwood pulp, hardwood pulp), cotton linters, corn fiber and other agricultural sources, and bacterial cellulose.

[0036] One method of producing cellulose esters is by esterification. In this method, cellulose is mixed with an appropriate organic acid, anhydride and / or catalyst and then converted into a cellulose triester. The esters are then hydrolyzed by adding a water-acid mixture to the cellulose triesters, which can then be filtered to remove any gel particles or fibers. Water is added to the mixture to precipitate the cellulose ester. The cellulose ester can then be washed with water to remove reaction byproducts, followed by dehydration and drying.

[0037] Acylating agents suitable for use herein may include, but are not limited to, alkyl or aryl carboxylic acid anhydrides, carboxylic acid halides and / or carboxylic acid esters containing the above-mentioned alkyl or aryl groups suitable for use in the acyl substituents of the substituted cellulose esters described herein. Examples of suitable carboxylic acid anhydrides include, but are not limited to, acetic anhydride, propionic anhydride, butyric anhydride, pivaloyl anhydride, benzoic anhydride and naphthoyl anhydride. Examples of carboxylic acid halides include, but are not limited to, acetyl, propionyl, butyryl, pivaloyl, benzoyl and naphthoyl chloride or bromide. Examples of carboxylic acid esters include, but are not limited to, acetyl, propionyl, butyryl, pivaloyl, benzoyl and naphthoyl methyl esters. In one or more embodiments, the acylating agent may be one or more carboxylic acid anhydrides selected from acetic anhydride, propionic anhydride, butyric anhydride, pivaloyl anhydride, benzoyl anhydride and naphthoyl anhydride.

[0038] In various embodiments, the cellulose triester to be hydrolyzed may have three substituents independently selected from alkanoyl groups having 2 to 12 carbon atoms. Examples of cellulose triesters include cellulose triacetate, cellulose tripropionate, cellulose tributyrate, or mixed triesters of cellulose, such as cellulose acetate propionate and cellulose acetate butyrate. These cellulose triesters may be prepared by many methods known to those skilled in the art. For example, cellulose triesters may be prepared by reacting the cellulose triesters with a catalyst such as H2SO4 to produce a cellulose triester. 4) Cellulose triesters can also be prepared by homogeneous acylation of cellulose dissolved in a suitable solvent such as LiCl / DMAc or LiCl / NMP.

[0039] After cellulose is esterified to triesters, some of the acyl substituents can be removed by hydrolysis or alcoholysis to obtain secondary cellulose esters. Secondary cellulose esters can also be prepared directly without hydrolysis by using a limited amount of acylating agent. This method is particularly useful when the reaction is carried out in a solvent that will dissolve cellulose.

[0040] The cellulose esters thus prepared generally contain the following structure:

[0041]

[0042] Where R 2 , R 3 and R 6 is hydrogen (provided that R 2 , R 3 and R 6 cannot be hydrogen at the same time), alkyl-acyl and / or aryl-acyl groups (such as those described above) bound to cellulose via ester linkages.

[0043] The cellulose esters prepared by these methods may have a degree of polymerization ("DP") of at least 10. In other embodiments, the cellulose esters may have a DP of at least 50, at least 100, or at least 250. In other embodiments, the cellulose esters may have a DP in the range of about 5 to about 100, or in the range of about 10 to about 50.

[0044] Acylating agents suitable for use herein may include, but are not limited to, alkyl or aryl carboxylic acid anhydrides, carboxylic acid halides and / or carboxylic acid esters containing the above-mentioned alkyl or aryl groups suitable for use in the acyl substituents of the substituted cellulose esters described herein. Examples of suitable carboxylic acid anhydrides include, but are not limited to, acetic anhydride, propionic anhydride, butyric anhydride, pivaloyl anhydride, benzoic anhydride and naphthoyl anhydride. Examples of carboxylic acid halides include, but are not limited to, acetyl, propionyl, butyryl, pivaloyl, benzoyl and naphthoyl chloride or bromide. Examples of carboxylic acid esters include, but are not limited to, acetyl, propionyl, butyryl, pivaloyl, benzoyl and naphthoyl methyl esters. In one or more embodiments, the acylating agent may be one or more carboxylic acid anhydrides selected from acetic anhydride, propionic anhydride, butyric anhydride, pivaloyl anhydride, benzoyl anhydride and naphthoyl anhydride.

[0045] The present application discloses, in a first aspect, a mixed ester cellulose ester ("MCE") comprising: (1) a plurality of acetyl substituents; (2) a plurality of propionyl substituents; and (3) a plurality of hydroxyl substituents, wherein: the MCE has an average degree of substitution ("DS") of acetyl substituents of 0.1 to 2.3. Ac ”), MCE has an average degree of substitution (“DS Pr ”), MCE has an average degree of substitution (“DS OH ”).

[0046] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, wherein DS Ac is at least 0.1, at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 1.0, at least 1.1, at least 1.2, at least 1.3, at least 1.4, at least 1.5, at least 1.6, at least 1.7, at least 1.8, at least 1.9, or at least 2.0, or from 1.8 to 2.3, or from 1.8 to 2.2, or from 1.8 to 2.1, or from 1.8 to 2.0, or from 1.85 to 2.3, or from 1.85 to 2.2, or from 1.85 to 2.1, or from 1.85 to 2.0, or from 1.9 to 2.3, or from 1.9 to 2.2, or from 1.9 to 2.1, or from 1.9 to 2.0. Additionally, or in the alternative, DS Ac Less than 2.3, or less than 2.2, or less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, or less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, or less than 0.7, or less than 0.5, or less than 0.4, or less than 0.3.

[0047] In one embodiment or in combination with any other embodiment, class, or subclass of this first aspect, wherein DS Ac from 0.6 to 2.2, or 0.6 to 2.1, or 0.6 to 2.0, or 0.6 to 1.9, or 0.6 to 1.8, or 0.7 to 2.3, or 0.7 to 2.2, or 0.7 to 2.1, or 0.7 to 2.0, or 0.7 to 1.9, or 0.8 to 2.3, or 0.8 to 2.2, or 0.8 to 2.1, or 0.8 to 2.0, or 0.8 to 1.9, or 0.9 to 2.3, or 0.9 to 2.2, or 0.9 to 2.1, or 0.9 to 2.0, or 0.9 to 1.9, or 1.0 to 2.3, or 1.0 1.9, or 0.7 to 1.5, or 0.7 to 1.3, or 0.7 to 1.1, or 0.7 to 0.9.

[0048] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, wherein DS Pr is at least 0.1, or at least 0.2, or at least 0.3, or at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4. Additionally, or in the alternative, DS Pr Less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, or less than 0.7, or less than 0.5, or less than 0.4, or less than 0.3.

[0049] In one embodiment or in combination with any other embodiment, class, or subclass of this first aspect, wherein DS PrFrom 0.1 to 0.9, or 0.1 to 0.85, or 0.1 to 0.8, or 0.1 to 0.75, or 0.1 to 0.7, or 0.1 to 0.6, or 0.1 to 0.5, or 0.1 to 0.4, or 0.15 to 0.95, or 0.15 to 0.9, or 0.15 to 0.85, or 0.15 to 0.8, or 0.15 to 0.75, or 0.15 to 0.7, or 0.15 to 0.65, or 0.2 to 0.95, or 0.2 to 0.9 , or 0.2 to 0.85, or 0.2 to 0.8, or 0.2 to 0.75, or 0.2 to 0.7, or 0.2 to 0.65, 0.25 to 0.95, or 0.25 to 0.9, or 0.25 to 0.85, or 0.25 to 0.8, or 0.25 to 0.75, or 0.25 to 0.7, or 0.25 to 0.65, or 0.3 to 0.95, or 0.3 to 0.9, or 0.3 to 0.85, or 0.3 to 0.8, or 0.3 to 0 .75, or 0.3 to 0.7, or 0.3 to 0.65, or 0.35 to 0.95, or 0.35 to 0.9, or 0.35 to 0.85, or 0.35 to 0.8, or 0.35 to 0.75, or 0.35 to 0.7, or 0.35 to 0.65, or 0.4 to 0.95, or 0.4 to 0.9, or 0.4 to 0.85, or 0.4 to 0.8, or 0.4 to 0.75, or 0.4 to 0.7, or 0.4 to 0.65, or 0. .45 to 0.95, or 0.45 to 0.9, or 0.45 to 0.85, or 0.45 to 0.8, or 0.45 to 0.75, or 0.45 to 0.7, or 0.45 to 0.65, or 0.5 to 0.95, or 0.5 to 0.9, or 0.5 to 0.85, or 0.5 to 0.8, or 0.5 to 0.75, or 0.5 to 0.7, or 0.5 to 0.65, or 0.1 to 0.9, or 0.1 to 0.85, or 0.1 to 0.8.

[0050] In one embodiment or in combination with any other embodiment, class, or subclass of this first aspect, wherein DS OH is at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or at least 1.5, or at least 1.6, or at least 1.7, or at least 1.8, or at least 1.9, or at least 2.0, or at least 2.1, or at least 2.2, or at least 2.3, or at least 2.4, or at least 2.5, or at least 2.6. Additionally, or in the alternative, DS OHLess than 2.8, or less than 2.7, or less than 2.6, or less than 2.5, or less than 2.4, or less than 2.3, or less than 2.2, or less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, or less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8.

[0051] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, wherein DS OH 0.5 to 1.5, or 0.5 to 1.45, or 0.5 to 1.40, or 0.5 to 1.35, or 0.5 to 1.30, or 0.5 to 1.25, or 0.5 to 1.2, or 0.5 to 1.15, or 0.5 to 1.1, or 0.5 to 1.05, or 0.5 to 1.0, or 0.5 to 0.95 or 0.5 to 0.9, or 0.55 to 1.5, or 0.55 to 1.45, or 0.55 to 1.40, or 0.55 to 1.35, or 0.55 to 1.30, or 0.55 to 1.25, or 0.55 to 1.2, or 0.55 to 1.15, or 0.55 to 1.1, or 0.55 to 1.05, or 0.55 to 1.0, or 0.55 to 0.95, or 0.55 to 0.9, or 0.6 to 1.5, or 0.6 to 1.45, or 0.6 to 1.40, or 0.6 to 1.35, or 0.6 to 1.30, or 0.6 to 1.25, or 0. 6 to 1.2, or 0.6 to 1.15, or 0.6 to 1.1, or 0.6 to 1.05, or 0.6 to 1.0, or 0.6 to 0.95, or 0.6 to 0.9, or 0.65 to 1.5, or 0.65 to 1.45, or 0.65 to 1.40, or 0.65 to 1.35, or 0.65 to 1.30, or 0.65 to 1.25, or 0.65 to 1.2, or 0.65 to 1.15, or 0.65 to 1.1, or 0. 7 to 1.2, or 0.7 to 1.15, or 0.7 to 1.1, or 0.7 to 1.05, or 0.7 to 1.0, or 0.7 to 0.95 or 0.65 to 0.9, or 0.7 to 1.5, or 0.7 to 1.45, or 0.7 to 1.40, or 0.7 to 1.35, or 0.7 to 1.30, or 0.7 to 1.25, or 0.7 to 1.2, or 0.7 to 1.15, or 0.7 to 1.1, or 0.7 to 1.05, or 0.7 to 1.0, or 0.7 to 0.95 or 0.7 to 0.9.

[0052] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, wherein DS Pr and DS AcThe sum of is 1.9 to 2.44, or 1.9 to 2.0, or 1.9 to 2.1, or 1.9 to 2.2, or 1.9 to 2.3, or 2.0 to 2.44, or 2.0 to 2.1, or 2.0 to 2.2, or 2.0 to 2.3, or 2.1 to 2.44, or 2.1 to 2.2, or 2.1 to 2.3, or 2.2 to 2.44, or 2.2 to 2.3.

[0053] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, the mixed cellulose ester has a ratio of hydroxyl substituents to acetyl substituents of at least 0.4:1, or at least 0.5:1, or at least 0.6:1, or at least 0.7:1, or at least 0.8:1, or at least 0.9:1, or at least 1:1, or at least 1.1:1, or at least 1.2:1, or at least 1.3:1, or at least 1.4:1, or at least 1.5:1, or at least 1.6:1, or at least 1.7:1, or at least 1.8:1, or at least 1.9:2, or at least 2:1. Additionally, in alternative embodiments, the ratio of hydroxyl substituents to acetyl substituents of the mixed cellulose ester is less than 2:1, or less than 1.9:1, or less than 1.8:1, or less than 1.7:1, or less than 1.6:1, or less than 1.5:1, or less than 1.4:1, or less than 1.3:1, or less than 1.2:1, or less than 1.1:1, or less than 1:1.

[0054] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, the MCE has a ratio of hydroxyl substituents to propionyl substituents of at least 0.4:1, or at least 0.5:1, or at least 0.6:1, or at least 0.7:1, or at least 0.8:1, or at least 0.9:1, or at least 1:1, or at least 1.1:1, or at least 1.2:1, or at least 1.3:1, or at least 1.4:1, or at least 1.5:1, or at least 1.6:1, or at least 1.7:1, or at least 1.8:1, or at least 1.9:2, or at least 2:1. Additionally or in the alternative, the MCE has a ratio of hydroxyl substituents to propionyl substituents of less than 2:1, or less than 1.9:1, or less than 1.8:1, or less than 1.7:1, or less than 1.6:1, or less than 1.5:1, or less than 1.4:1, or less than 1.3:1, or less than 1.2:1, or less than 1.1:1, or less than 1:1.

[0055] In one embodiment or in combination with any other embodiments, classes or subclasses of this first aspect, the MCE exhibits at least 40% biodegradability, at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, or at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 56 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0056] In one embodiment or in combination with any other embodiments, classes or subclasses of this first aspect, the MCE exhibits at least 40% biodegradability, or at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0057] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, the MCE has a weight average molecular weight in the range of 5,000 to 100,000 Da, or 5,000 to 50,000 Da, or 5,000 to 25,000 Da, or 15,000 to 100,000 Da, or 15,000 to 50,000 Da, or 15,000 to 25,000 Da, or 50,000 to 100,000 Da, or 75,000 to 100,000 Da, or 15,000 to 250,000 Da.

[0058] The present application discloses, in a second aspect, a mixed cellulose ester ("MCE") comprising: (1) a plurality of acetyl substituents; (2) a plurality of propionyl substituents; and (3) a plurality of hydroxyl substituents, wherein: the MCE has an average degree of substitution ("DS") of acetyl substituents of 0.1 to 1.9. Ac ”), MCE has an average degree of substitution (“DS Pr ”), and the MCE has an average degree of substitution (“DS OH ”).

[0059] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS Ac is at least 0.1, or at least 0.2, or at least 0.3, or at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or at least 1.5, or at least 1.6, or at least 1.7, or at least 1.8, or at least 1.9, or at least 2.0. Additionally, or in the alternative, DS Ac Less than 2.3, or less than 2.2, or less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, or less than 0.7, or less than 0.5, or less than 0.4, or less than 0.3.

[0060] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS Ac is from 0.6 to 0.7, or from 0.6 to 0.8, or from 0.6 to 0.9, or from 0.6 to 1.0, or from 0.6 to 1.1, or from 0.7 to 0.9, or from 0.7 to 1.0, or from 0.7 to 1.1, or from 0.7 to 1.2, or from 0.8 to 0.9, or from 0.8 to 1.0, or from 0.8 to 1.1, or from 0.8 to 1.2, or from 0.9 to 1.0, or from 0.9 to 1.1, or from 0.9 to 1.2, or from 1.0 to 1.1, or from 1.0 to 1.2, or from 1.1 to 1.2.

[0061] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS Pr is at least 0.1, or at least 0.2, or at least 0.3, or at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4. Additionally, or in the alternative, DS Pr Less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, or less than 0.7, or less than 0.5, or less than 0.4, or less than 0.3.

[0062] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS Pris from 1.05 to 1.35, or from 1.05 to 1.3, or from 1.05 to 1.25, or from 1.05 to 1.2, or from 1.05 to 1.15, or from 1.05 to 1.1, or from 1.1 to 1.4, or from 1.1 to 1.35, or from 1.1 to 1.3, or from 1.1 to 1.25, or from 1.1 to 1.2, or from 1.1 to 1.15, or from 1.15 to 1.4, or 1.15 to 1.35, or 1.15 to 1.3, or 1.15 to 1.25, or 1.15 to 1.2, or 1.2 to 1.4, or 1.2 to 1.35, or 1.2 to 1.3, or 1.2 to 1.25, or 1.25 to 1.4, or 1.25 to 1.35, or 1.25 to 1.3, or 1.3 to 1.4, or 1.3 to 1.35.

[0063] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS OH is at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or at least 1.5, or at least 1.6, or at least 1.7, or at least 1.8, or at least 1.9, or at least 2.0, or at least 2.1, or at least 2.2, or at least 2.3, or at least 2.4, or at least 2.5, or at least 2.6. Additionally, or in the alternative, DS OH Less than 2.8, or less than 2.7, or less than 2.6, or less than 2.5, or less than 2.4, or less than 2.3, or less than 2.2, or less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, or less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8.

[0064] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS OH75 to 1.35, or 0.7 to 1.3, or 0.7 to 1.25, or 0.7 to 1.2, or 0.7 to 1.15, or 0.7 to 1.1, or 0.7 to 1.05, or 0.7 to 1.0, or 0.7 to 0.95, or 0.7 to 0.9, or 0.7 to 0.85, or 0.7 to 0.8, or 0.7 to 0.75, or 0.75 to 1.4, or 0.75 to 1.35, or 0.75 to 1.3, or 0.75 to 1.25, or 0.75 to 1.2, or 0.75 to 1.15, or 0.75 to 1.1, or 0.75 to 1.05, or 0.75 to 1.0, or 0.75 to 0.95, or 0. 8 to 1.4, or 0.8 to 1.35, or 0.8 to 1.3, or 0.8 to 1.25, or 0.8 to 1.2, or 0.8 to 1.15, or 0.8 to 1.1, or 0.8 to 1.05, or 0.85 to 1.4, or 0.85 to 1.35, or 0.85 to 1.3, or 0.85 to 1.25, or 0.85 to 1.2, or 0.85 to 1.15, or 0.85 to 1.1, or 0.85 to 1.05, or 0.9 to 1.4, or 0.9 to 1.35, or 0.9 to 1.3, or 0.9 to 1.25, or 0.9 to 1.2, or 0.9 to 1.15, or 0.9 to 1.1, or 0.9 to 1.05.

[0065] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS Pr and DS Ac the sum of is 1.65 to 2.3, or 1.65 to 2.2, or 1.65 to 2.1, or 1.65 to 2.0, or 1.65 to 1.9, or 1.65 to 1.8, or 1.7 to 2.3, or 1.7 to 2.2, or 1.7 to 2.1, or 1.7 to 2.0, or 1.7 to 1.9, or 1.7 to 1.8, or 1.75 to 2.3, or 1.75 to 2.2, or 1.75 to 2.1, or 1.75 to 2.0, or 1.75 to 1.9, or 1.8 to 2.3, or 1.8 to 2.2, or 1.8 to 2.1, or 1.8 to 2.0, or 1.8 to 1.9, or 1.9 to 2.3, or 1.9 to 2.2, or 1.9 to 2.1, or 1.9 to 2.0, or 2.0 to 2.3, or 2.0 to 2.2, or 2.0 to 2.1.

[0066] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, wherein DS OH0.6 to 0.7, or 0.7 to 1.35, or 0.7 to 1.3, or 0.7 to 1.25, or 0.7 to 1.2, or 0.7 to 1.15, or 0.7 to 1.1, or 0.7 to 1.05, or 0.7 to 1.0, or 0.7 to 0.95, or 0.7 to 0.9, or 0.7 to 0.85, or 0.7 to 0.8, or 0.7 to 0.75, or 0.75 to 1.4, or 0.75 to 1.35, or 0.75 to 1.3, or 0.75 to 1.25, or 0.75 to 1.2, or 0.75 to 1.15, or 0.75 to 1.1, or 0.75 to 1.05, or 0.75 to 1.0, or 0.75 to 0.95 , or 0.8 to 1.4, or 0.8 to 1.35, or 0.8 to 1.3, or 0.8 to 1.25, or 0.8 to 1.2, or 0.8 to 1.15, or 0.8 to 1.1, or 0.8 to 1.05, or 0.85 to 1.4, or 0.85 to 1.35, or 0.85 to 1.3, or 0.85 to 1.25, or 0.85 to 1.2, or 0.85 to 1.15, or 0.85 to 1.1, or 0.85 to 1.05, or 0.9 to 1.4, or 0.9 to 1.35, or 0.9 to 1.3, or 0.9 to 1.25, or 0.9 to 1.2, or 0.9 to 1.15, or 0.9 to 1.1, or 0.9 to 1.05.

[0067] In one embodiment or in combination with any other embodiment, class, or subclass of this second aspect, the mixed cellulose ester has a ratio of hydroxyl substituents to acetyl substituents of at least 0.4:1, or at least 0.5:1, or at least 0.6:1, or at least 0.7:1, or at least 0.8:1, or at least 0.9:1, or at least 1:1, or at least 1.1:1, or at least 1.2:1, or at least 1.3:1, or at least 1.4:1, or at least 1.5:1, or at least 1.6:1, or at least 1.7:1, or at least 1.8:1, or at least 1.9:2, or at least 2:1. Additionally, in alternative embodiments, the ratio of hydroxyl substituents to acetyl substituents of the mixed cellulose ester is less than 2:1, or less than 1.9:1, or less than 1.8:1, or less than 1.7:1, or less than 1.6:1, or less than 1.5:1, or less than 1.4:1, or less than 1.3:1, or less than 1.2:1, or less than 1.1:1, or less than 1:1.

[0068] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, the MCE has a ratio of hydroxyl substituents to propionyl substituents of at least 0.4:1, or at least 0.5:1, or at least 0.6:1, or at least 0.7:1, or at least 0.8:1, or at least 0.9:1, or at least 1:1, or at least 1.1:1, or at least 1.2:1, or at least 1.3:1, or at least 1.4:1, or at least 1.5:1, or at least 1.6:1, or at least 1.7:1, or at least 1.8:1, or at least 1.9:2, or at least 2:1. Additionally or in the alternative, the MCE has a ratio of hydroxyl substituents to propionyl substituents of less than 2:1, or less than 1.9:1, or less than 1.8:1, or less than 1.7:1, or less than 1.6:1, or less than 1.5:1, or less than 1.4:1, or less than 1.3:1, or less than 1.2:1, or less than 1.1:1, or less than 1:1.

[0069] In one embodiment or in combination with any other embodiments, classes or subclasses of this second aspect, the MCE exhibits at least 40% biodegradability, at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, or at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 56 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0070] In one embodiment or in combination with any other embodiments, classes or subclasses of this second aspect, the MCE exhibits at least 40% biodegradability, at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, or at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0071] In one embodiment or in combination with any other embodiment, class or subclass of this second aspect, the MCE has a weight average molecular weight in the range of 5,000 to 100,000 Da, or 5,000 to 50,000 Da, or 5,000 to 25,000 Da, or 15,000 to 100,000 Da, or 15,000 to 50,000 Da, or 15,000 to 25,000 Da, or 50,000 to 100,000 Da, or 75,000 to 100,000 Da, or 15,000 to 250,000 Da.

[0072] The present application also discloses a mixed cellulose ester ("MCE") in a third aspect, comprising: (1) a plurality of acetyl substituents; (2) a plurality of butyryl substituents; and (3) a plurality of hydroxyl substituents, wherein: the MCE has an average degree of substitution ("DS") of acetyl substituents of 0.1 to 2.4. Ac ”), MCE has an average degree of substitution (“DS Bu ”), MCE has an average degree of substitution (“DS OH ”).

[0073] In one embodiment or in combination with any other embodiment, class or subclass of this first aspect, wherein DS Ac is at least 0.1, or at least 0.2, at least 0.3, or at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or at least 1.5, or at least 1.6, or at least 1.7, or at least 1.8, or at least 1.9, or at least 2.0. Additionally, or in the alternative, DS Ac Less than 2.3, or less than 2.2, or less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, or less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, or less than 0.7, or less than 0.5, or less than 0.4, or less than 0.3.

[0074] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, wherein DS Ac0.9 to 2.4, or 0.9 to 2.3, or 0.9 to 2.2, or 0.9 to 2.1, or 0.9 to 2.0, or 0.9 to 1.9, or 0.9 to 1.8, or 0.9 to 1.7, or 0.9 to 1.6, or 0.9 to 1.4, or 0.9 to 1.3, or 0.9 to 1.2, or 0.9 to 1.1, or 0.9 to 1.0 , or 0.92 to 2.4, or 0.92 to 2.3, or 0.92 to 2.2, or 0.92 to 2.1, or 0.92 to 2.0, or 0.92 to 1.9, or 0.92 to 1.8, or 0.92 to 1.7, or 0.92 to 1.6, or 0.92 to 1.4,0.92 to 1.3, or 0.92 to 1.2, or 0.92 to 1.1, or 0.92 to 1.0, or 0.94 to 2.4, 0.94 to 2.3, or 0.94 to 2.2, or 0.94 to 2.1, or 0.94 to 2.0, or 0.94 to 1.9, or 0.94 to 1.8, or 0.94 to 1.7, or 0.94 to 1.6, or 0.94 to 1.4, 0.94 to 1.3, or 0 0.94 to 1.2, or 0.94 to 1.1, or 0.94 to 1.0, or 0.96 to 2.4, or 0.96 to 2.3, or 0.96 to 2.2, or 0.96 to 2.1, or 0.96 to 2.0, or 0.96 to 1.9, or 0.96 to 1.8, or 0.96 to 1.7, or 0.96 to 1.6, or 0.96 to 1 .4, 0.96 to 1.3, or 0.96 to 1.2, or 0.96 to 1.1, or 0.96 to 1.0, or 0.98 to 2.4, 0.98 to 2.3, or 0.98 to 2.2, or 0.98 to 2.1, or 0.98 to 2.0, or 0.98 to 1.9, or 0.98 to 1.8, or 0.98 to 1.7, or 0.9 8 to 1.6, or 0.98 to 1.4, or 0.98 to 1.3, or 0.98 to 1.2, or 0.98 to 1.1, or 0.98 to 1.0, or 1.0 to 2.4, or 1.0 to 2.3, or 1.0 to 2.2, or 1.0 to 2.1, or 1.0 to 2.0, or 1.0 to 1.9, or 1.0 to 1.8, or 1.0 to 1. 7, or 1.0 to 1.6, or 1.0 to 1.4, or 1.0 to 1.3, 1.0 to 1.2, or 1.0 to 1.1, or 1.1 to 2.4, or 1.1 to 2.3, or 1.1 to 2.2, or 1.1 to 2.1, or 1.1 to 2.0, or 1.1 to 1.9, or 1.1 to 1.8, or 1.1 to 1.7, or 1.1 to 1. 6, or 1.1 to 1.4, or 1.1 to 1.3, or 1.1 to 1.2, or 1.2 to 2.4, or 1.2 to 2.3, or 1.2 to 2.2, or 1.2 to 2.1, or 1.2 to 2.0, or 1.2 to 1.9, or 1.2 to 1.8, or 1.2 to 1.7, or 1.2 to 1.6, or 1.2 to 1.4, or 1.2 to 1.3, or 1.3 to 2.4, or 1.3 to 2.3, or 1.3 to 2.2, or 1.3 to 2.1, or 1.3 to 2.0, or 1.3 to 1.9, or 1.3 to 1.8, or 1.3 to 1.7, or 1.3 to 1.6, or 1.3 to 1.4, or 1.4 to 2.4, or 1.4 to 2.3, or 1.4 to 2.2, or 1.4 to 2.1, or 1.4 to 2.0, or 1.4 to 1.9, or 1.4 to 1.8, or 1.4 to 1.7, or 1.4 to 1.6, or 1.5 to 2.4, or 1.5 to 2.3, or 1.5 to 2.2, or 1.5 to 2.1, or 1.5 to 2.0, or 1.5 to 1.9, or 1.5 to 1.8, or 1.5 to 1.7, or 1.5 to 1.6, or 1.6 to 2.4, or 1.5 to 2.3, or 1.5 to 2.2, or 1.5 to 2.1, or 1.5 to 2.0, or 1.5 to 1.9, or 1.5 to 1.8, or 1.5 to 1.7, or 1.5 to 1.6, or 1.6 to 2.4, or 1. 6 to 2.3, or 1.6 to 2.2, or 1.6 to 2.1, or 1.6 to 2.0, or 1.6 to 1.9, or 1.6 to 1.8, or 1.6 to 1.7, or 1.7 to 2.4, or 1.7 to 2.3, or 1.7 to 2.2, or 1.7 to 2.1, or 1.7 to 2.0, or 1.7 to 1.9, or 1.7 to 1.8, or 1.8 to 2.3, or 1.8 to 2.1, or 1.8 to 2.0, or 1.8 to 1.9, or 1.9 to 2.3, or 1.9 to 2.2, or 1.9 to 2.1, or 1.9 to 2.0, or 2.0 to 2.4, or 2.0 to 2.3, or 2.0 to 2.2, or 2.0 to 2.1, or 2.1 to 2.4, or 2.1 to 2.3, or 2.1 to 2.2, or 2.2 to 2.3. .

[0075] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, wherein DS Bu is at least 0.2, or at least 0.3, or at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or from 0.18 to 0.23, or from 0.18 to 0.22, or from 0.18 to 0.21, or from 0.18 to 0.20, or from 0.18 to 0.19, or from 0.19 to 0.23, or from 0.19 to 0.22, or from 0.19 to 0.21, or from 0.19 to 0.2, or from 0.2 to 0.23, or from 0.2 to 0.22, or from 0.2 to 0.21. Additionally, or in the alternative, DS Bu Less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, or less than 0.7, or less than 0.5, or less than 0.4, or less than 0.3.

[0076] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, wherein DS Bu0.1 to 1.35, or 0.1 to 1.3, or 0.1 to 1.25, or 0.1 to 1.2, or 0.1 to 1.15, or 0.1 to 1.1, or 0.1 to 1.0, or 0.1 to 0.8, or 0.1 to 0.6, or 0.2 to 1.35, or 0.2 to 1.3, or 0.2 to 1.25, or 0.2 to 1.2, or 0. 0.2 to 1.15, or 0.2 to 1.1, or 0.2 to 1.0, or 0.2 to 0.8, or 0.2 to 0.6, or 0.2 to 0.4, or 0.3 to 1.35, or 0.3 to 1.3, or 0.3 to 1.25, or 0.3 to 1.2, or 0.3 to 1.15, or 0.3 to 1.1, or 0.3 to 1.0, or 0.3 to 0 .8, or 0.3 to 0.6, or 0.3 to 0.5, or 0.4 to 1.35, or 0.4 to 1.3, or 0.4 to 1.25, or 0.4 to 1.2, or 0.4 to 1.15, or 0.4 to 1.1, or 0.4 to 1.0, or 0.4 to 0.8, or 0.4 to 0.6, or 0.5 to 1.35, or 0.5 to 1.3, or 0.5 to 1.25, or 0.5 to 1.2, or 0.5 to 1.15, or 0.5 to 1.1, or 0.5 to 1.0, or 0.5 to 0.8, or 0.5 to 0.7, or 0.6 to 1.35, or 0.6 to 1.3, or 0.6 to 1.25, or 0.6 to 1.2, or 0.6 to 1.15, or 0.6 to 1.1, or 0.6 to 1.0, or 0.6 to 0.8, or 0.7 to 1.35, or 0.7 to 1.3, or 0.7 to 1.25, or 0.7 to 1.2, or 0.7 to 1.15, or 0.7 to 1.1, or 0.7 to 1.0, or 0.8 to 1.35, or 0.8 to 1.3, or 0.8 to 1.25, or 0.8 to 1.2, or 0.8 to 1 .15, or 0.8 to 1.1, or 0.8 to 1.0, or 0.9 to 1.35, or 0.9 to 1.3, or 0.9 to 1.25, or 0.9 to 1.2, or 0.9 to 1.15, or 0.9 to 1.1, or 1.0 to 1.35, or 1.0 to 1.3, or 1.0 to 1.25, or 1.0 to 1.2, or 1.0 to 1.1 5, or 1.0 to 1.1, or 1.05 to 1.35, or 1.05 to 1.3, or 1.05 to 1.25, or 1.05 to 1.2, or 1.05 to 1.15, or 1.05 to 1.1, or 1.1 to 1.4, or 1.1 to 1.35, or 1.1 to 1.3, or 1.1 to 1.25, or 1.1 to 1.2, or 1.1 to 1.15, or 1.15 to 1.4, or 1.15 to 1.35, or 1.15 to 1.3, or 1.15 to 1.25, or 1.15 to 1.2, or 1.2 to 1.4, or 1.2 to 1.35, or 1.2 to 1.3, or 1.2 to 1.25, or 1.25 to 1.4, or 1.25 to 1.35, or 1.25 to 1.3, or 1.3 to 1.4, or 1.3 to 1.35. .

[0077] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, wherein DS OH is at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or 0.5 to 0.95, or 0.5 to 0.93, or 0.5 to 0.91, or 0.5 to 0.9, or 0.5 to 0.85, or 0.5 to 0.80, or 0.5 to 0.75, or 0.5 to 0.7 or 0.5 5 to 0.95, or 0.55 to 0.93, or 0.55 to 0.91, or 0.55 to 0.9, or 0.55 to 0.85, or 0.55 to 0.80, or 0.55 to 0.75, or 0.55 to 0.7, or 0.6 to 0.95, or 0.6 to 0.93, or 0.6 to 0.91, or 0.6 to 0.9, or 0.6 to 0.85, or 0.6 to 0.80, or 0.6 to 0.75, or 0.6 to 0.7, or 0.65 to 0.95, or 0.65 to 0.93, or 0.65 to 0.91, or 0.65 to 0.9, or 0.65 to 0.85, or 0.65 to 0.80, or 0.65 to 0.75, or 0.65 to 0.7, or 0.7 to 0.95, or 0.7 to 0.93, or 0.7 to 0.91, or 0.7 to 0.9, or 0.7 to 0.9 .85, or 0.7 to 0.80, or 0.7 to 0.75, or 0.8 to 0.95, or 0.8 to 0.93, or 0.8 to 0.91, or 0.8 to 0.9, or 0.8 to 0.85, or 0.85 to 0.95, or 0.85 to 0.93, or 0.85 to 0.91, or 0.85 to 0.9, or 0.9 to 0.95, or 0.9 to 0.93, or 0.9 to 0.91. Additionally, or in the alternative, DS OH Less than 2.8, less than 2.7, or less than 2.6, or less than 2.5, or less than 2.4, or less than 2.3, or less than 2.2, or less than 2.1, less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, or less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8.

[0078] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, wherein DS OHis from 0.5 to 1.0, or from 0.5 to 0.95, or from 0.5 to 0.9, or from 0.5 to 0.85, or from 0.5 to 0.8, or from 0.5 to 0.75, or from 0.5 to 0.7, or from 0.5 to 0.65, or from 0.5 to 0.6, or from 0.5 to 0.55, or from 0.55 to 1.0, or from 0.55 to 0.95, or from 0.55 to 0.9, or from 0.55 to 0.85, or from 0.55 to 0.8, or from 0.55 to 0.75, or from 0.55 to 0.7, or or 0.65 to 0.75, or 0.6 to 0.8, or 0.6 to 0.85, or 0.6 to 0.9, or 0.6 to 0.95, or 0.6 to 1.0, or 0.65 to 0.7, or 0.65 to 0.75, or 0.65 to 0.8, or 0.65 to 0.85, or 0.65 to 0.9, or 0.65 to 0.95, or 0.65 to 1.0.

[0079] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, wherein DS Bu and DS Ac The sum of is 1.65 to 2.3, or 1.65 to 2.2, or 1.65 to 2.1, or 1.65 to 2.0, or 1.65 to 1.9, or 1.65 to 1.8, or 1.7 to 2.3, or 1.7 to 2.2, or 1.7 to 2.1, or 1.7 to 2.0, or 1.7 to 1.9, or 1.7 to 1.8, or 1.75 to 2.3, or 1.75 to 2.2, or 1.7 5 to 2.1, or 1.75 to 2.0, or 1.75 to 1.9, or 1.8 to 2.3, or 1.8 to 2.2, or 1.8 to 2.1, or 1.8 to 2.0, or 1.8 to 1.9, or 1.9 to 2.3, or 1.9 to 2.2, or 1.9 to 2.1, or 1.9 to 2.0, or 2.0 to 2.4, or 2.0 to 2.3, or 2.0 to 2.2, or 2.0 to 2.1.

[0080] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, the mixed cellulose ester has a ratio of hydroxyl substituents to acetyl substituents of at least 0.4:1, or at least 0.5:1, or at least 0.6:1, or at least 0.7:1, or at least 0.8:1, or at least 0.9:1, or at least 1:1, or at least 1.1:1, or at least 1.2:1, or at least 1.3:1, or at least 1.4:1, or at least 1.5:1, or at least 1.6:1, or at least 1.7:1, or at least 1.8:1, or at least 1.9:2, or at least 2:1. Additionally, in alternative embodiments, the ratio of hydroxyl substituents to acetyl substituents of the mixed cellulose ester is less than 2:1, or less than 1.9:1, or less than 1.8:1, or less than 1.7:1, or less than 1.6:1, or less than 1.5:1, or less than 1.4:1, or less than 1.3:1, or less than 1.2:1, or less than 1.1:1, or less than 1:1.

[0081] In one embodiment or in combination with any other embodiment, class, or subclass of this third aspect, the mixed cellulose ester has a ratio of hydroxyl substituents to butyryl substituents of at least 0.4:1, or at least 0.5:1, or at least 0.6:1, or at least 0.7:1, or at least 0.8:1, or at least 0.9:1, or at least 1:1, or at least 1.1:1, or at least 1.2:1, or at least 1.3:1, or at least 1.4:1, or at least 1.5:1, or at least 1.6:1, or at least 1.7:1, or at least 1.8:1, or at least 1.9:2, or at least 2:1. Additionally, or in the alternative, the mixed cellulose ester has a ratio of hydroxyl substituents to butyryl substituents of less than 2:1, or less than 1.9:1, or less than 1.8:1, or less than 1.7:1, or less than 1.6:1, or less than 1.5:1, or less than 1.4:1, or less than 1.3:1, or less than 1.2:1, or less than 1.1:1, or less than 1:1.

[0082] In one embodiment or in combination with any other embodiment, the mixed cellulose ester is cellulose acetate butyrate, or cellulose acetate butyrate, or a mixture thereof. In a class of this embodiment, the mixed cellulose ester is cellulose acetate butyrate. In a class of this embodiment, the mixed cellulose ester is cellulose acetate propionate. In a class of this embodiment, the mixed cellulose ester is a mixture comprising cellulose acetate butyrate or cellulose acetate propionate.

[0083] In one embodiment or in combination with any other embodiments, classes or subclasses of this third aspect, the MCE exhibits at least 40% biodegradability, or at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, or at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 90% biodegradability at 56 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0084] In one embodiment or in combination with any other embodiments, classes or subclasses of this third aspect, the MCE exhibits at least 40% biodegradability, or at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, or at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0085] In one embodiment or in combination with any other embodiment, class or subclass of this third aspect, the MCE has a weight average molecular weight in the range of 5,000 to 100,000 Da, or 5,000 to 50,000 Da, or 5,000 to 25,000 Da, or 15,000 to 100,000 Da, or 15,000 to 50,000 Da, or 15,000 to 25,000 Da, or 50,000 to 100,000 Da, or 75,000 to 100,000 Da, or 15,000 to 250,000 Da.

[0086] In one embodiment or in combination with any of the embodiments mentioned herein, CE 100 can be the mixed cellulose ester of the first aspect, the second aspect, and / or the third aspect (including any classes or subclasses of these aspects).

[0087] Solvent system

[0088] The solvent system (e.g., solvent 102) is generally capable of dissolving the CE to produce a dispersed phase / solid phase of an emulsion / dispersion as described herein. In one embodiment or in combination with any of the embodiments mentioned herein, the solvent 102 can consist of a single solvent component, or can be a solvent system comprising a plurality of solvent components. The plurality of solvent components can include at least two solvent components, at least three solvent components, or a total of three solvent components.

[0089] In one embodiment or in combination with any of the embodiments mentioned herein, the solvent 102 includes at least one, at least two, or all three of a C1-C4 alkyl acetate, a C1-C4 alcohol, and water. The C1-C4 alkyl acetate may include one or more of methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, and sec-butyl acetate. The C1-C4 alcohol may include one or more of methanol, ethanol, propanol (e.g., isopropanol, n-propanol, and isopropanol), and butanol (e.g., n-butanol, isobutanol, sec-butanol, and tert-butanol).

[0090] In one embodiment or in combination with any of the embodiments mentioned herein, when solvent 102 comprises more than one solvent component, the C1-C4 alkyl acetate can be present in one or more of the following amounts: (1) at least 10 wt%, or 25 wt%, 50 wt%, or 60 wt%, or 70 wt%; (2) no more than 99 wt%, or 95 wt%, or 90 wt%, or 85 wt%, or 80 wt%; and (3) in the range of 10-99 wt%, or 25-95 wt%, or 50-90 wt%, or 70-85 wt%.

[0091] In one embodiment or in combination with any of the embodiments mentioned herein, when the solvent 102 comprises more than one solvent component, the C1-C4 alcohol is present in one or more of the following amounts: (1) at least 1 wt%, or 2 wt%, or 4 wt%, or 6 wt%, or 8 wt%, or 10 wt%; (2) no more than 80 wt%, or 60 wt%, or 40 wt%, or 30 wt%, or 20 wt%, or 15 wt%; and (3) in the range of 1-80 wt%, or 2-60 wt%, or 4-40 wt%, or 6-30 wt%, or 8-20 wt%, or 10-15 wt%.

[0092] In one embodiment or in combination with any of the embodiments mentioned herein, when solvent 102 comprises more than one solvent component, water is present in one or more of the following amounts: (1) at least 1 wt%, or 2 wt%, or 4 wt%, or 6 wt%, or 8 wt%; (2) no more than 50 wt%, or 25 wt%, or 20 wt%, or 15 wt%; and (3) in the range of 1-50 wt%, or 2-25 wt%, 4-30 wt%, or 6-20 wt%, or 8-15 wt%.

[0093] In one embodiment or in combination with any embodiment mentioned herein, the solvent 102 includes at least one, at least two, or all three of ethyl acetate, n-propanol, and water. In such an embodiment, ethyl acetate is present in an amount in the range of 50-90 wt%, or 55-90 wt%, or 60-90 wt%, or 65-90 wt%, or 65-85 wt%, or 70-85 wt%, or 75-85 wt%, n-propanol is present in an amount in the range of 4-40 wt%, or 5-35 wt%, or 6-30 wt%, or 7-25 wt%, or 8-20 wt%, or 10-20 wt%, or 10-15 wt%, and water is present in an amount in the range of 4-30 wt%, or 5-25 wt%, or 6-20 wt%, or 7-15 wt%, or 8-12 wt%, or 9-12 wt%.

[0094] Surprisingly, it has been found that water helps and / or enables the solubilization of certain mixed cellulose esters. In particular, it has been found that water helps and / or enables the solubilization of highly biodegradable mixed cellulose esters (such as cellulose esters with a DS greater than a determined threshold). OH These findings are disclosed in the Examples section below.

[0095] Hydrocolloid

[0096] Hydrocolloids as described herein, such as hydrocolloid 106, are used as colloid protectants and / or viscosity builders. In one embodiment or in combination with any embodiment mentioned herein, hydrocolloid 106 is a lyophilic colloid. For example, hydrocolloid 106 may include at least one of gelatin, natural gum, protein, or cellulose derivatives. The cellulose derivative may include one or both of methyl cellulose and carboxymethyl cellulose.

[0097] The hydrocolloid, such as carboxymethylcellulose, can be selected based on the desired viscosity of the resulting aqueous mixture. In one embodiment or in combination with any of the embodiments mentioned herein, a "low" viscosity hydrocolloid has a viscosity in the range of 10-50 cps, a "medium" viscosity hydrocolloid has a viscosity in the range of 400-800 cps, and a "high" viscosity hydrocolloid has a viscosity in the range of 1500-3000 cps.

[0098] Surfactant system

[0099] In one embodiment or in combination with any of the embodiments mentioned herein, the surfactant 108 includes two or more separate emulsifiers. These separate emulsifiers can be distinguished based on their hydrophilic-lipophilic balance (HLB) values. For example, when the surfactant 108 includes two separate emulsifiers, the emulsifiers can include a lower HLB emulsifier and a higher HLB emulsifier.

[0100] In one embodiment or in combination with any of the embodiments mentioned herein, the HLB value of the higher HLB emulsifier is at least 6, or 8, or 10, or 12, or 14, or 16, or 18, and the HLB value of the lower HLB emulsifier does not exceed 12, or 10, or 8, or 6, or 4.

[0101] In one embodiment or in combination with any of the embodiments mentioned herein, the HLB value of the higher HLB emulsifier is at least one of: (1) at least 2, 4, 8, 10, 12 or 14 higher than the HLB value of the lower HLB emulsifier; (2) no more than 25, or 20, or 15; or (3) within the range of 2-25, or 8-20, or 12-15.

[0102] In one embodiment or in combination with any of the embodiments mentioned herein, the lower HLB emulsifier is glyceryl ester of stearic acid.In one embodiment or in combination with any of the embodiments mentioned herein, the higher HLB emulsifier is a secondary alcohol ethoxylate.

[0103] In one embodiment or in combination with any embodiment mentioned herein, the surfactant 108 further comprises a third emulsifier. The HLB value of the third emulsifier is greater than the HLB value of the lower HLB emulsifier. In one embodiment or in combination with any embodiment mentioned herein, the third emulsifier is a polyethylene glycol ester of stearic acid.

[0104] When surfactant 108 is formed from all three emulsifiers, the lower HLB emulsifier and the third emulsifier may be present in a ratio of at least 0.25: 1, or 0.5: 1, or 0.75: 1, or 1: 1, or 1.25: 1, or 1.5: 1, or 1.75: 1, or 2: 1 and / or no more than 5: 1, or 4: 1, or 3: 1, or 2: 1, or 1.75: 1, or 1.5: 1, or 1.25: 1. The lower HLB emulsifier and the third emulsifier may be defined as a combined emulsifier. Additionally, the higher HLB emulsifier and the combined emulsifier may be present in surfactant 108 in a ratio of at least 0.25:1, or 0.5:1, or 0.75:1, or 1:1, or 1.25:1, or 1.5:1, or 1.75:1, or 2:1 and / or no more than 5:1, or 4:1, or 3:1, or 2:1, or 1.75:1, or 1.5:1, or 1.25:1.

[0105] Reference now Figure 2 , the illustrated method for making the CE microbeads 112 includes separately forming a CE coating 136 and an aqueous mixture 138. The CE coating 136 and the aqueous mixture 138 are then combined to form the CE microbeads 112. For example, the CE coating 136 can be formed at block 140, and the aqueous mixture 138 can be formed at block 142. The CE coating 136 and the aqueous mixture 138 can then be combined at block 144 to form an emulsion and / or dispersion, as will be described in more detail below.

[0106] In one embodiment or in combination with any of the embodiments mentioned herein, CE coating 136 is formed from CE 100 , solvent 102 , water 104 , and, in some embodiments, recycled solvent 146 derived from rich solvent stream 134 .

[0107] In one embodiment or in combination with any of the embodiments mentioned herein, CE 100 is present in the CE coating in one or more of the following: (1) at least 1 wt%, or 2 wt%, or 4 wt%, or 6 wt%, or 8 wt%, or 10 wt%; (2) no more than 80 wt%, or 60 wt%, or 40 wt%, or 30 wt%, or 20 wt%, or 15 wt%; and (3) in the range of 1-80 wt%, or 2-60 wt%, or 4-40 wt%, or 6-30 wt%, or 8-20 wt%, or 10-15 wt%.

[0108] In one embodiment or in combination with any of the embodiments mentioned herein, when the solvent 102 comprises a C1-C4 alkyl acetate, the C1-C4 alkyl acetate is present in the CE coating 136 in one or more of the following amounts: (1) at least 10 wt%, 25 wt%, 50 wt%, 60 wt%, or 65 wt%; (2) no more than 95 wt%, or 90 wt%, or 85 wt%, or 80 wt% or 75 wt%; and (3) in the range of 10-95 wt%, or 25-90 wt%, or 50-85 wt%, or 65-75 wt%.

[0109] In one embodiment or in combination with any of the embodiments mentioned herein, when the solvent 102 comprises a C1-C4 alcohol, the C1-C4 alcohol is present in the CE coating 136 in one or more of the following amounts: (1) at least 1 wt%, or 2 wt%, or 4 wt%, or 6 wt%, or 8 wt%; (2) no more than 50 wt%, or 25 wt%, or 20 wt%, or 15 wt%; and (3) in the range of 1-50 wt%, or 2-25 wt%, or 4-30 wt%, or 6-20 wt%, or 8-15 wt%.

[0110] In one embodiment or in combination with any other embodiment, the ratio of solvent to CE used to dissolve to form CE coating 136 is at least 1:1, or 2:1, or 3:1, or 4:1, or 5:1 and / or no more than 100:1, or 50:1, or 25:1, or 10:1.

[0111] In one embodiment or in combination with any of the embodiments mentioned herein, when the solvent 102 comprises water, the water is present in the CE coating 136 in one or more of the following amounts: (1) at least 0.5 wt%, or 1 wt%, or 2 wt%, or 4 wt%, or 6 wt%; (2) no more than 40 wt%, or 25 wt%, or 15 wt%, or 10 wt%; and (3) in the range of 0.5-40 wt%, or 1-25 wt%, or 2-15 wt%, or 4-20 wt%, or 6-10 wt%.

[0112] In a particular embodiment, CE coating 136 is formed from CE 100 , solvent 102 including ethyl acetate and n-propanol, and water 104 . In such an embodiment, CE is present in the CE coating 136 in an amount in the range of 6-30 wt%, or 7-25 wt%, or 8-20 wt%, or 9-20 wt%, or 10-15 wt% or 12-15 wt%, ethyl acetate is present in the CE coating 136 in an amount in the range of 50-85 wt%, or 55-85 wt%, or 60-85 wt%, or 65-85 wt%, or 70-85 wt% or 75-85 wt%, n-propanol is present in the CE coating 136 in an amount in the range of 4-30 wt%, or 6-25 wt%, or 8-20 wt%, or 10-20 wt%, or 12-15 wt%, and water is present in the CE coating 136 in an amount in the range of 4-20 wt%, or 5-18 wt%, or 6-16 wt%, or 7-14 wt%, or 8-12 wt%.

[0113] In one embodiment or in combination with any of the embodiments mentioned herein, CE 100, solvent 102, and water 104 are combined at unit 140 until substantially homogeneous to produce CE coating 136. In one embodiment or in combination with any of the embodiments mentioned herein, the components are mixed at room temperature (e.g., at least 15°C, or 20°C, or 25°C, or 30°C and / or no more than 45°C, or 40°C, or 35°C, or 30°C, or 25°C, or 20°C) for a duration of at least 1, or 2, or 5, or 10, or 15, or 20, or 25, or 30, or 45, or 60, or 120, or 240 minutes and / or for as long as necessary to produce a substantially homogeneous mixture.

[0114] In one embodiment or in combination with any of the embodiments mentioned herein, aqueous mixture 138 is formed from water 104, hydrocolloid 106, surfactant 108, and, in some embodiments, recycled solvent 146 derived from rich solvent stream 134. Optionally, additional solvent 148 can be added to units 140 and / or 142 as needed to maintain the concentrations of the solvent components at suitable levels.

[0115] In one embodiment or in combination with any of the embodiments mentioned herein, the ratio of the recycled solvent portion to the fresh solvent portion used in the units 140 and / or 142 is at least 2.5:1, or 10:1, 25:1, or 50:1, or 75:1, or 90:1, or 95:1, or 99:1 by weight, and / or does not exceed 1000:1, or 500:1, or 200:1 or 100:1 by weight.

[0116] In one embodiment or in combination with any of the embodiments mentioned herein, the compositional make-up of the recycled solvent differs from the compositional make-up of the fresh solvent by no more than 10 wt%, or 5 wt%, or 2 wt%, or 1 wt% in total.

[0117] In one embodiment or in combination with any of the embodiments mentioned herein, the fresh solvent and the recycled solvent portion have substantially the same composition.

[0118] In one embodiment or in combination with any of the embodiments mentioned herein, water is present in the aqueous mixture 138 in one or more of the following amounts: (1) at least 40 wt%, or 60 wt%, or 70 wt%, or 80 wt%, or 85 wt%; (2) no more than 99 wt%, or 97 wt%, or 95 wt%, or 94 wt%, or 92 wt%; and (3) in the range of 40-99 wt%, or 70-95 wt%, or 85-92 wt%.

[0119] In one embodiment or in combination with any of the embodiments mentioned herein, the hydrocolloid is present in the aqueous mixture 138 in one or more of the following amounts: (1) at least 0.001 wt %, or 0.005 wt %, or 0.01 wt %, or 0.05 wt %, or 0.1 wt %; (2) no more than 15 wt %, or 10 wt %, or 5 wt %, or 2 wt %, or 1 wt %; and (3) in the range of 0.001-15 wt %, or 0.01-5 wt %, or 0.1-2 wt %.

[0120] In one embodiment or in combination with any of the embodiments mentioned herein, the surfactant is present in the aqueous mixture 138 in one or more of the following amounts: (1) at least 0.005 wt%, or 0.01 wt%, or 0.05 wt%, or 0.1 wt%, or 0.5 wt%; (2) no more than 15 wt%, or 10 wt%, or 5 wt%, 2 wt%, or 1.5 wt%; and (3) in the range of 0.005-15 wt%, or 0.05-5 wt%, or 0.5-1.5 wt%.

[0121] As described above, the surfactants described herein may include a higher HLB emulsifier and a lower HLB emulsifier. In such embodiments, the higher HLB emulsifier and the lower HLB emulsifier are present in the aqueous mixture 138 in a ratio of high HLB emulsifier to low HLB emulsifier in a range of at least 0.25:1, or 0.5:1, 1:1, or 1.5:1, or 1.75:1 and / or no more than 10:1, or 5:1, or 3:1, or 2.5:1 and / or in a range of 0.25:1-10:1, or 0.5:1-5:1, or 1:1-3:1.

[0122] Reference again Figure 2 In some embodiments, the additional solvent 148 and / or recycled solvent 146 are received at unit 142. In such embodiments, the solvent used to form the CE coating 136 and the aqueous mixture 138 is a common C1-C4 alkyl acetate. The use of at least one common component in the solvent systems received at units 140 and 142 facilitates the separation, recovery, and reuse of the solvent as described herein.

[0123] In one embodiment or in combination with any of the embodiments mentioned herein, when aqueous mixture 138 comprises C1-C4 alkyl acetate, the C1-C4 alkyl acetate is present in aqueous mixture 138 in one or more of the following amounts: (1) at least 1 weight percent, 2 weight percent, 4 weight percent, 6 weight percent, or 8 weight percent; (2) no more than 50 weight percent, 40 weight percent, 30 weight percent, 20 weight percent, or 15 weight percent; and (3) within the range of 1-50 weight percent, 2-40 weight percent, or 6-20 weight percent.

[0124] In one embodiment or in combination with any of the embodiments mentioned herein, the C1-C4 alkyl acetate is present in the aqueous mixture 138 in an amount (in wt %) within 25 wt %, 20 wt %, 15 wt %, 10 wt %, 5 wt % or 2 wt % of the solubility (in wt %) of the C1-C4 alkyl acetate in water at 20°C.

[0125] The C1-C4 alkyl acetate can be one or both of methyl acetate and ethyl acetate. In one embodiment or in combination with any of the embodiments mentioned herein, when the C1-C4 alkyl acetate is ethyl acetate, the ethyl acetate is present in the aqueous mixture in an amount in the range of 2-25 wt%, 4-20 wt%, 6-15 wt% or 8-10 wt%. In one embodiment or in combination with any of the embodiments mentioned herein, when the C1-C4 alkyl acetate is methyl acetate, the methyl acetate is present in the aqueous mixture in an amount in the range of 5-50 wt%, 10-40 wt%, 15-35 wt% or 20-30 wt%.

[0126] In a particular embodiment, the aqueous mixture 138 is formed from water 104, hydrocolloid 106, surfactant 108, and C1-C4 alkyl acetate. In such embodiments, water is present in the aqueous mixture 138 in an amount in the range of 70-95 wt%, 75-95 wt%, 80-95 wt%, 85-95 wt%, or 87.5-92.5 wt%, the hydrocolloid is present in the aqueous mixture 138 in an amount in the range of 0.01-5 wt%, 0.1-4 wt%, 0.5-3 wt%, 0.6-2 wt%, 0.7-1 wt%, or 0.8-0.9 wt%, the surfactant is present in the aqueous mixture 138 in an amount in the range of 0.05- %, 0.1-5 wt %, 0.1-4 wt %, 0.5-3 wt %, 0.6-2 wt %, 0.7-1 wt % or 0.8-1 wt %, and C1-C4 alkyl acetate is present in aqueous mixture 138 in an amount within the range of 2-40 wt %, 3-35 wt %, 4-30 wt %, 5-25 wt %, 5-20 wt %, 5-15 wt %, 5-10 wt % or 6-10 wt %.

[0127] In one embodiment or in combination with any of the embodiments mentioned herein, water 104, hydrocolloid 106, surfactant 108, and optional C1-C4 alkyl acetate are combined at unit 142 to produce aqueous mixture 138. In one embodiment or in combination with any of the embodiments mentioned herein, these components are mixed at a temperature of at least 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, or 50°C and / or not exceeding 100°C, 75°C, 50°C, 40°C, 35°C, 30°C, 25°C, or 20°C for a duration of at least 1, 2, 5, 10, 15, 20, 25, 30, 45, 60, 120, or 240 minutes and / or for as long as required to produce a substantially homogenous mixture, depending on the viscosity of the hydrocolloid used.

[0128] Emulsion / dispersion formation

[0129] Once formed, CE coating 136 and aqueous mixture 138 may be combined at unit 144 to produce an emulsion and / or dispersion, as described above.

[0130] In one embodiment or in combination with any of the embodiments mentioned herein, the ratio of CE coating 136 to aqueous mixture 138 combined at unit 144 to form the initial emulsion is at least 0.05:1 to 10:1, 0.1:1 to 5:1, 0.2:1 to 2:1, or 0.4:1 to 0.8:1.

[0131] In one embodiment or in combination with any of the embodiments mentioned herein, the initial emulsion comprises water in an amount of at least 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, or 60 wt% and / or not more than 90 wt%, 80 wt%, 70 wt%, 60 wt%, 50 wt% or 40 wt%.

[0132] Once combined, the initial emulsion is converted into a pre-hardened dispersion comprising a solid phase and a liquid phase. This conversion can be performed by at least one of shear, spray (ultrasonic or electro), and membrane emulsion.

[0133] In one embodiment or in combination with any of the embodiments mentioned herein, the combined CE coating and aqueous mixture is recirculated through a high shear mixer to disperse the solid phase within the liquid phase and promote the hardening of the solid phase to produce initial microparticles. This shearing can be performed as the CE coating 136 and aqueous mixture 138 are fed into the unit 144 and / or can be performed after a predetermined amount of the CE coating 136 and aqueous mixture 138 are in the unit 144.

[0134] In one embodiment or in combination with any of the embodiments mentioned herein, the combined CE coating and aqueous mixture is cycled through the high shear mixer for at least 1, 2, 3, 4, or 5 residence times and / or no more than 20, 15, 10, 9, or 8 residence times (based on the total volume of the high shear mixer used). In addition, high shear mixing is performed for a duration of at least 1, 2, 5, 10, 15, 20, 25, 30, 45, 60, 120, or 240 minutes, and / or for as long as necessary to cycle the volume of the mixture for the predetermined number of residence times.

[0135] To produce the initial microparticles that will form the CE microbeads as described herein, the combined CE coating and aqueous mixture is agitated in unit 144. The agitation performed at unit 144 can be quantified by at least one of: (1) impeller tip speed, (2) impeller Reynolds number, and (3) power-to-weight ratio. In one embodiment or in combination with any of the embodiments mentioned herein, the high shear mixing is performed at an impeller tip speed of at least 25, 50, 75, 100, 150, 200, 250, or 300 cm / s, and / or no more than 1000, 500, 400, 300, 200, or 100 cm / s. In one embodiment or in combination with any of the embodiments mentioned herein, the high shear mixing is performed at an impeller Reynolds number of at least 500, 1000, 1500, 2000, 3000, 4000, 5000 or 6000, and / or no more than 15000, 10000, 8000, 6000, 5000, 4000 or 3000. In one embodiment or in combination with any of the embodiments mentioned herein, the high shear mixing is performed at a power to mass ratio of at least 0.01, 0.02, 0.03, 0.1, 0.5, 1.0, 1.5, 2.0, 2.5 or 3.0, and / or no more than 10.0, 7.5, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, 1.0, 0.5 or 0.1.

[0136] As used herein, terms such as "solid," "solid phase," "particles," and "particulates" refer to semisolid materials that do not lose their discrete properties (ie, flow together) when the aqueous / continuous phase surrounding the material is removed.

[0137] Hardening with extractant

[0138] The pre-hardened dispersion 150 formed at unit 144 and containing the initial particles (i.e., solid phase) can be directed to a hardening unit 152 to convert the initial particles into hardened CE microbeads 112. At unit 152, the initial particles contained in the pre-hardened dispersion 150 are contacted with an extractant 154 (i.e., flooding liquid) to produce a hardened dispersion 156. That is, the contacting step is conducive to desolventizing and hardening the initial particles into CE microbeads. In one embodiment or in combination with any embodiment mentioned herein, the extractant is water. Alternatively, the extractant can be methanol, ethanol, and combinations thereof.

[0139] In one embodiment or in combination with any of the embodiments mentioned herein, the pre-hardened dispersion and extractant are combined at unit 152 at an extractant to dispersion weight ratio of at least 0.5:1, 1:1, 1.5:1, 2:1 or 1.5:1, and / or no more than 10:1, 8:1, 6:1, 4:1 or 3:1.

[0140] In one embodiment or in combination with any embodiment mentioned herein, the weight ratio of extractant to pre-hardened particles used in the contacting step is at least 2:1, 5:1, 10:1, 20:1, 30:1 or 40:1, and / or no more than 200:1, 100:1, 80:1, 60:1 or 50:1.

[0141] Thus, in one embodiment or in combination with any of the embodiments mentioned herein, the hardened dispersion 156 has one or more of the following amounts of water: (1) at least 25 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, 85 wt%, or 90 wt%; (2) no more than 99 wt%, 97.5 wt%, 95 wt%, 92.5 wt%, 90 wt%, 80 wt%, 70 wt%, 60 wt%, or 50 wt%; and (3) in the range of 50-99 wt%, 70-95 wt%, or 80-92.5 wt%.

[0142] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened dispersion 156 has a weight concentration of water that is at least 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 times, and / or no more than 100, 70, 50, 25, 15, 10, 5, or 2.5 times the weight concentration of water in the initial emulsion.

[0143] In one embodiment or in combination with any of the embodiments mentioned herein, the hardening of the particles is performed under agitation. The agitation performed at unit 152 can be quantified by at least one of the following: (1) impeller tip speed, (2) impeller Reynolds number, and (3) power-to-mass ratio. In one embodiment or in combination with any of the embodiments mentioned herein, the conversion / hardening is performed at an impeller tip speed of at least 25, 50, 75, 100, 150, 200, 250, or 300 cm / s, and / or no more than 1000, 500, 400, 300, 200, or 100 cm / s. In one embodiment or in combination with any of the embodiments mentioned herein, the conversion / hardening is carried out at an impeller Reynolds number of at least 500, 1000, 1500, 2000, 3000, 4000, 5000 or 6000, and / or no more than 15000, 10000, 8000, 6000, 5000, 4000 or 3000. In one embodiment or in combination with any of the embodiments mentioned herein, the conversion / hardening is carried out at a power-to-weight ratio of at least 0.01, 0.02, 0.03, 0.1, 0.5, 1.0, 1.5, 2.0, 2.5 or 3.0, and / or no more than 10.0, 7.5, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, 1.0, 0.5 or 0.1.

[0144] Furthermore, conversion / hardening is carried out for a period of at least 0.1, 0.5, 1, 2, 4, 6, 8, 10 or 20 minutes, and / or for a period of no more than 12, 8, 6, 4 or 2 hours, and at a temperature of at least 0°C, 5°C or 10°C, and / or no more than 100°C, 75°C, 50°C or 25°C.

[0145] In one embodiment or in combination with any embodiment mentioned herein, the conversion / hardening is carried out in a single container or multiple containers. Based on the output of the CE microbeads to be produced and the volume capacity of the available containers for hardening, multiple containers may be required. In an embodiment using multiple containers, a first portion of the pre-hardened dispersion 150 can be received at a first hardening unit, and a second portion of the pre-hardened dispersion can be received at a second hardening unit. Flow communication can then be provided between the separate hardening units to enhance mass transfer, thereby accelerating the desolvation of the initial microparticles.

[0146] In one embodiment or in combination with any of the embodiments mentioned herein, the pre-hardened dispersion 150 has a solids content of at least 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, or 4 wt%, and / or no more than 40 wt%, 30 wt%, 20 wt%, 10 wt%, or 6 wt%.

[0147] As a result of hardening, in one embodiment or in combination with any of the embodiments mentioned herein, the hardened dispersion 156 has a solids content of at least 0.05 wt%, 0.1 wt%, 0.5 wt%, or 1 wt%, and / or no more than 20 wt%, 10 wt%, 5 wt%, 2 wt%, or 1 wt%.

[0148] In one embodiment or in combination with any of the embodiments mentioned herein, the solids content of the pre-hardened dispersion is at least 1.5, 2, 3, or 4 times, and / or no more than 20, 10, 8, or 6 times, the solids content of the hardened dispersion. In other words, at unit 152, the solvent is extracted from the initial microparticles to produce a hardened dispersion 156 comprising hardened CE microbeads 112 and a flooding liquid filled with solvent.

[0149] CE Bead Isolation / Separation

[0150] Any suitable technique may be used to separate and recover the CE microbeads 112 from the hardened dispersion 156 at unit 158. In one embodiment or in combination with any of the embodiments mentioned herein, the separation may be performed by at least one, at least two, or all three of the following: (1) flashing one or more liquid components from the hardened CE microbeads; (2) filtering the hardened CE microbeads from the one or more liquid components; and (3) centrifuging, redispersing, and drying the hardened microbeads.

[0151] Solid state processing and / or CE bead separation can be performed as Figure 1 In a single unit as shown in FIG. , or it can be Figure 2 The diagram is shown in Figure 1 and is performed in multiple units. Figure 2 , a wet solids stream 160 and a separated mother liquor stream 162 are discharged from unit 158. The wet solids stream 160 contains hardened CE microbeads and residual liquid. In one embodiment or in combination with any of the embodiments mentioned herein, the wet solids stream 160 has a solids content of at least 10 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, or 45 wt%, and / or no more than 60 wt%, 65 wt%, 50 wt%, 45 wt%, or 40 wt%. This enables the wet solids stream 160 to be transported to downstream units while reducing plugging and processing problems.

[0152] The wet solids stream 160 may then optionally be processed in a washing unit 164 and a second solid / liquid separation unit 166. At unit 164, the hardened CE microbeads are washed with water 122 to produce a washed solids stream 168. The washed solids stream 168 is then processed at unit 166 by at least one, at least two, or all three of the following: (1) flashing one or more liquid components from the hardened CE microbeads; (2) filtering the hardened CE microbeads from the one or more liquid components; and (3) centrifuging, redispersing, and drying the hardened microbeads. This second solid / liquid separation step advantageously reduces the solvent content in the liquid surrounding the hardened CE microbeads.

[0153] The wash liquid 130 may be recovered from the second solid / liquid separation step and then recycled for use as at least a portion of the aqueous mixture in unit 142 and / or for use as at least a portion of the flooding liquid in unit 152 .

[0154] In one embodiment or in combination with any of the embodiments mentioned herein, at least 1 wt%, 5 wt%, or 10 wt%, and / or no more than 90 wt%, 50 wt%, 20 wt%, or 10 wt% of the aqueous mixture 138 is recycled scrubber liquor.

[0155] In one embodiment or in combination with any of the embodiments mentioned herein, at least 1 wt%, 5 wt%, or 10 wt%, and / or no more than 90 wt%, 50 wt%, 20 wt%, or 10 wt% of the flooding liquid 154 used in unit 152 is recycled wash liquid.

[0156] The wet solids stream 172 discharged from unit 166 is then received at a drying unit 170. In one embodiment or in combination with any of the embodiments mentioned herein, drying is performed at unit 170 under agitation and with the addition of heat. Such agitation is beneficial in reducing aggregation of the recovered CE microbeads 112. The characteristics of the recovered CE microbeads 112 will be described in more detail below.

[0157] In one embodiment or in combination with any of the embodiments mentioned herein, the drying unit 170 is a rotary cone dryer.

[0158] Fluid processing and recycling

[0159] The separated mother liquor stream 162 discharged from unit 164 can be processed to recover water and / or solvent. The recovered water and / or solvent can then be recycled to Figure 2 One or more of the units shown in can be combined to improve the economic efficiency of the microbead formation method described herein.

[0160] Liquid processing can be Figure 1 In a single unit as shown in FIG. , or it can be Figure 2 The diagram is shown in Figure 1 and is performed in multiple units. Figure 2 , for example, mother liquor stream 162 contains at least a portion of the water and at least a portion of the solvent introduced at units 140 and / or 142. Mother liquor stream 162 may also contain residual amounts of hydrocolloids, surfactants, and any components used to make mixed cellulose esters.

[0161] The mother liquor stream 162 may be heated 174 and then separated into at least two separate streams, such as a solvent-rich stream 134 and a water-rich (solvent-depleted) stream 132, at unit 176. The mother liquor stream 162 may be separated at unit 176 using any suitable technique. In one embodiment or in combination with any of the embodiments mentioned herein, the liquid separation may be performed by distillation or the like.

[0162] In one embodiment or in combination with any of the embodiments mentioned herein, the water-rich stream 132 comprises one or more of: (1) water; (2) a surfactant; (3) a hydrocolloid; and (4) a C1-C4 alkyl acetate.

[0163] Thus, the water-rich stream 132 may be cooled 181 and then recycled to Figure 2142 for forming aqueous mixture 138 and / or to unit 152 as stream 180 for desolvation of initial microparticles, thereby reducing the amount of water required for such processes. For example, any excess material not required for these processes can be purged from the system and subjected to wastewater treatment.

[0164] In one embodiment or in combination with any of the embodiments mentioned herein, the ratio of recycled water in stream 180 used in the hardening step to recycled water in stream 178 used in forming the aqueous mixture 138 is at least 1:1, 1.5:1, 2:1, 3:1, 4:1, and / or no more than 20:1, 10:1, 8:1 or 6:1.

[0165] In one embodiment or in combination with any embodiment mentioned herein, the ratio of recycled water to purified water in stream 180 used in the hardening step is at least 1:1, 1.5:1, 2:1, 3:1, 4:1, and / or no more than 20:1, 10:1, 8:1 or 6:1.

[0166] In one embodiment or in combination with any of the embodiments mentioned herein, at least 75%, 90%, 95%, 98%, 99% or 100% by weight of the extractant used in unit 152 is recycled water recovered downstream from unit 152, such as water contained in water-rich stream 132 that is recycled to unit 152.

[0167] In one embodiment or in combination with any of the embodiments mentioned herein, fresh water 154 is added to unit 152 for the hardening step.

[0168] In one embodiment or in combination with any of the embodiments mentioned herein, the ratio of the total amount of fresh water added to the total amount of purified water is at least 0.25:1, 0.5:1, 0.75:1 or 0.9:1, and / or no more than 4:1, 2:1, 1.5:1, 1.25:1, or 1.1:1.

[0169] In one embodiment or in combination with any of the embodiments mentioned herein, the rich solvent stream 134 includes one or more of: (1) C1-C4 alkyl acetate; (2) C1-C4 alcohol; and (3) water.

[0170] Thus, the rich solvent stream 134 may be recycled to Figure 2For example, the composition of rich solvent stream 134 enables it to be recycled to at least one of units 140 for use as a portion of the solvent in the formation of CE coating 136, and / or to unit 142 for use in forming aqueous mixture 138. Any excess material not required for these processes can be purged from the system.

[0171] In one embodiment or in combination with any of the embodiments mentioned herein, at least 75 wt%, 90 wt%, 95 wt%, 98 wt%, 99 wt%, or 100 wt% of the solvent used in unit 140 for forming CE coating 136 is recycled solvent 146 .

[0172] In one embodiment or in combination with any of the embodiments mentioned herein, fresh water 104 is added to unit 142 for forming aqueous mixture 138 .

[0173] In one embodiment or in combination with any of the embodiments mentioned herein, the ratio of the combined amount of water in streams 178 and 180 to the total amount of fresh water 104 added in unit 142 is at least 2:1, 4:1, 6:1, or 8:1.

[0174] In one embodiment or in combination with any of the embodiments mentioned herein, aqueous mixture 138 comprises an azeotrope of water and a C1-C4 alkyl acetate and / or an azeotrope of water and a C1-C4 alcohol derived from water-rich stream 132 .

[0175] Hydroxyl groups are generally strong hydrogen bonders. Therefore, as the DS of a given substance increases, OH As the number of carbon atoms (i.e., C1-C4) increases, the chance of hydrogen bonding also increases. The co-solvent alcohol of the solvent system described herein is also a strong hydrogen bonder. However, surprisingly, it was found that as the number of carbon atoms (i.e., C1-C4) increases, the ability of the co-solvent alcohol to form hydrogen bonds decreases. Thus, it was found that a lower carbon number binary solvent system without water was able to dissolve DS with a biodegradability greater than the threshold. OH (For example, a DS greater than 0.8 OH ) cellulose esters. In contrast, it was found that higher carbon number binary solvent systems without water were unable to dissolve DS with biodegradability greater than the same threshold. OH Thus, it has been found that in a solvent system containing a higher carbon number alcohol, the presence of a strong hydrogen bonding agent (ie, water) that is substantially free of steric hindrance facilitates the dissolution of the mixed CE described herein in the solvent system.

[0176] In one embodiment or in combination with any of the embodiments mentioned herein, the recycled solvent 146 contains water in an amount of at least 1 wt%, 2 wt%, 4 wt%, 6 wt%, or 8 wt%, and / or no more than 50 wt%, 40 wt%, 30 wt%, 20 wt%, or 10 wt%.

[0177] In one embodiment or in combination with any of the embodiments mentioned herein, the recycle solvent 146 contains at least one azeotrope, wherein the azeotrope contains water and another component.

[0178] In one embodiment or in combination with any of the embodiments mentioned herein, an azeotrope can be in the recycle solvent 146 and can be a water / alcohol azeotrope, a water / alkyl acetate azeotrope, or both a water / alcohol azeotrope and a water / alkyl acetate azeotrope.

[0179] In one embodiment or in combination with any of the embodiments mentioned herein, the recycle solvent 146 contains multiple azeotropes. In one embodiment or in combination with any of the embodiments mentioned herein, the multiple azeotropes include multiple binary azeotropes. In one embodiment or in combination with any of the embodiments mentioned herein, the components of the solvent system are selected such that the recycle solvent 146 does not contain any ternary azeotropes, thereby simplifying recovery and recycling of the solvent.

[0180] In one embodiment or in combination with any of the embodiments mentioned herein, the rich solvent stream 134 contains less than 10 wt%, less than 1 wt%, less than 0.1 wt%, or 0.0 wt% ternary azeotrope.

[0181] In one embodiment or in combination with any of the embodiments mentioned herein, the recycle solvent 146 contains a total of three binary azeotropes, such as a water / alcohol azeotrope, a water / alkyl acetate azeotrope, and an alcohol / alkyl acetate azeotrope.

[0182] Additional embodiments

[0183] Reference now Figure 3 , CE microbeads 112 are produced by continuous particle formation. In an exemplary embodiment, particle formation begins at unit 142 where water 104, hydrocolloid 106, surfactant 108, and, in some embodiments, recycled solvent 146 from rich solvent stream 134 are combined to form aqueous mixture 138.

[0184] Aqueous mixture 138 is discharged from unit 142 and received at dispersion forming unit 182. At unit 182, aqueous mixture 138 is combined with CE 100, solvent 102, and optionally recycled solvent 146 from rich solvent stream 134. Thus, rather than forming CE coating 136 and aqueous mixture 138 in separate units, aqueous mixture 138, CE 100, and solvent 102 are combined in a common unit to form an initial emulsion.

[0185] In one embodiment or in combination with any of the embodiments mentioned herein, the aqueous mixture 138, CE 100, and solvent 102 are agitated in unit 182 and the combined CE coating and aqueous mixture are circulated through a high shear mixer to disperse the solid phase within the liquid phase of the initial emulsion and promote hardening of the solid phase to produce initial microparticles.

[0186] To produce the initial particles, the combined aqueous mixture 138, CE 100, and solvent 102 are agitated at unit 182. The agitation performed at unit 182 can be quantified by at least one of: (1) impeller tip speed, (2) impeller Reynolds number, and (3) power-to-mass ratio. In one embodiment or in combination with any of the embodiments mentioned herein, the high shear mixing is performed at an impeller tip speed of at least 25, 50, 75, 100, 150, 200, 250, or 300 cm / s, and / or no more than 1000, 500, 400, 300, 200, or 100 cm / s. In one embodiment or in combination with any of the embodiments mentioned herein, the high shear mixing is performed at an impeller Reynolds number of at least 500, 1000, 1500, 2000, 3000, 4000, 5000 or 6000, and / or no more than 15000, 10000, 8000, 6000, 5000, 4000 or 3000. In one embodiment or in combination with any of the embodiments mentioned herein, the high shear mixing is performed at a power to mass ratio of at least 0.01, 0.02, 0.03, 0.1, 0.5, 1.0, 1.5, 2.0, 2.5 or 3.0, and / or no more than 10.0, 7.5, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, 1.0, 0.5 or 0.1.

[0187] The pre-hardened dispersion 150 is then discharged from the unit 182 and the hardened CE microbeads 112 are recovered therefrom as described above.

[0188] refer to Figure 4 , CE microbeads 112 are produced by separate coating and aqueous mixture formation and combined emulsion / dispersion formation and particle hardening. In an exemplary embodiment, the particle formation is as follows Figure 21 , where the CE coating 136 and aqueous mixture 138 are formed in separate units.

[0189] However, in Figure 4 In the embodiment of the present invention, CE coating 136 and aqueous mixture 138 are fed into a common emulsion / dispersion formation and particle hardening unit 184. At unit 184, CE coating 136 and aqueous mixture 138 are combined and agitated to form an initial emulsion as described herein. Once the initial emulsion is formed, extractant 154 is fed directly into unit 184 to desolventize the initial microparticles.

[0190] refer to Figure 5 , CE microbeads 112 are produced by combined emulsion / dispersion formation. In an exemplary embodiment, particle formation is initiated by combining CE 100, solvent 102, water 104, hydrocolloid 106, surfactant 108, and optional recycled solvent 146 and recycled water 178 all in common unit 186. This mixture is agitated as described herein to produce a pre-hardened dispersion 150 containing initial microparticles. The pre-hardened dispersion is received at unit 152 to desolventize the initial microparticles as described herein.

[0191] refer to Figure 6 , CE microbeads 112 are produced by combined emulsion / dispersion formation and particle hardening. In an exemplary embodiment, particle formation begins by combining CE 100, solvent 102, water 104, hydrocolloid 106, surfactant 108, and optional recycled solvent 146 and recycled water 178 all in a common unit 188. At unit 188, these components are combined and agitated to form an initial emulsion as described herein. Once the initial emulsion is formed, the extractant 154 is fed directly into unit 188 to desolventize the initial microparticles.

[0192] refer to Figure 7 , CE microbeads 112 are produced by flash evaporation of solvent prior to particle hardening. In an exemplary embodiment, the pre-hardened dispersion 150 discharged from unit 144 is received at flash unit 190 instead of being received at particle hardening unit 152. At unit 144, at least some of the solvent of the pre-hardened dispersion 150 is removed from its liquid phase to thereby form a solvent-depleted dispersion 192 having a reduced solvent content. The solvent-depleted dispersion 192 is received at unit 152 to harden the pre-hardened microparticles contained therein as described above. The flashed solvent stream 194 discharged from unit 190 can be directed to unit 176 for liquid processing and recycling thereof.

[0193] In one embodiment or in combination with any of the embodiments mentioned herein, the removal at unit 144 is performed by pervaporation, cross-flow membrane filtration (ultrafiltration or nanofiltration), flash tanks, spray tanks, or wiped film evaporation.

[0194] In one embodiment or in combination with any of the embodiments mentioned herein, the removal at unit 144 reduces the solvent in the dispersion by at least 30 wt %, at least 50 wt %, at least 75 wt %, at least 90 wt %, between 30 wt % and 90 wt %, or between 50 wt % and 75 wt %.

[0195] In one embodiment or in combination with any of the embodiments mentioned herein, the solvent-depleted dispersion 192 has a solids content of at least 3 wt%, 4 wt%, 5 wt%, or 6 wt%, and / or no more than 40 wt%, 30 wt%, 20 wt%, or 10 wt%.

[0196] In one embodiment or in combination with any of the embodiments mentioned herein, the volume ratio of flooding liquid to the dispersion used in unit 152 is less than 2.5:1, 2:1, 1.75:1, 1.5:1, 1.25:1, or 1:1.

[0197] Hardened or jet-milled CE microbeads

[0198] The hardened or jet-milled CE microbeads produced by the methods disclosed herein exhibit desirable tactile and / or optical qualities, e.g., tactile and / or optical qualities that make them suitable for use in personal care products, cosmetics, etc. As used herein, the terms "microparticles," "beads," and "microbeads" are used interchangeably with the terms "hardened CE microbeads" or "jet-milled CE microbeads."

[0199] In one embodiment or in combination with any of the embodiments mentioned herein, the CE microbeads are produced at a rate of at least 50, 100, 250, 500, 1000, 2500, 5000 or 10000 kg / day, and / or no more than 100000, 75000 or 50000 kg / day. To achieve these production rates, CE, solvent and / or water are provided in the system at one or more of the following corresponding rates.

[0200] In one embodiment or in combination with any of the embodiments mentioned herein, CE is provided at unit 140 at a rate of at least 50, 100, 250, 500, 1000, 2500, 5000 or 10000 kg / day, and / or no more than 100000, 75000 or 50000 kg / day.

[0201] In one embodiment or in combination with any of the embodiments mentioned herein, solvent is provided at unit 140 at a rate of at least 50, 100, 250, 500, 1000, 2500, 5000 or 10000 kg / day, and / or no more than 100000, 75000 or 50000 kg / day.

[0202] In one embodiment or in combination with any of the embodiments mentioned herein, water is provided at unit 152 at a rate of at least 500, 1000, 2500, 5000, 10000, 25000, 50000, or 100000 kg / day, and / or no more than 1000000, 750000, or 500000 kg / day.

[0203] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened CE microbeads have a hardness at 20°C greater than the hardness at 20°C of the initial microparticles contained within the pre-hardened dispersion 150 and / or formed during any of the processes described herein.

[0204] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened CE microbeads have a hardness that is at least 1.1, 1.25, 1.5, 1.75 or 2 times the hardness of the initial microbeads.

[0205] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened CE microbeads have a solvent content of less than 100, 50, 25 or 10 ppm.

[0206] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a solvent content that is lower than the solvent content of the initial microparticles.

[0207] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a solvent content that is less than 0.99, 0.95, 0.9, 0.8, 0.7, 0.6 or 0.5 of the solvent content of the initial microparticles.

[0208] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a solvent content that is at least 1 wt%, 2 wt%, 4 wt%, 8 wt%, 12 wt%, 16 wt% or 20 wt% lower than the solvent content of the initial microparticles.

[0209] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a D50 volume-based particle size that is within 50%, 25%, 15%, 10%, 5% or 2% of the D50 particle size of the initial microparticles.

[0210] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a D50 volume-based particle size that is 0.99, 0.95, 0.9, 0.8, 0.7, 0.6 or 0.5 less than the D50 volume-based particle size of the initial microparticles.

[0211] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a particle size of 1 to 100, 1 to 80, 1 to 70, 1 to 60, 1 to 50, 1 to 40, 1 to 35, 1 to 30, 1 to 25, 1 to 20, 1 to 15, 1 to 10, 2 to 100, 2 to 80, 2 to 70, 2 to 60, 2 to 50, 2 to 40, 2 to 35, 2 ... 2 to 25, 2 to 20, 2 to 15, 2 to 10, 3 to 100, 3 to 80, 3 to 70, 3 to 60, 3 to 50, 3 to 40, 3 to 35, 3 to 30, 3 to 25, 3 to 20, 3 to 15, 3 to 10, 5 to 100, 5 to 80, 5 to 70, 5 to 60, 5 to 50, 5 to 40, 5 to 35, 5 to 30, 5 to 25, 5 to 20, 5 to 15, 5 to 10, 10 to 100, 10 to 80, 10 to 70, 10 to 60, 10 to 50, 10 to 40, 10 to 35, 10 to 30, 10 to 25, 10 to 20, 10 to 15, 15 to 100, 15 to 80, 15 to 70, 15 to 60, 15 to 50, 15 to 40, 15 to 35, 15 to 30, 15 to 25, 15 to 20, 20 to 100, 20 to 80, 20 to 7 Particle size based on D50 volume in the range of 0, 20 to 60, 20 to 50, 20 to 40, 20 to 35, 20 to 30, 25 to 100, 25 to 80, 25 to 70, 25 to 60, 25 to 50, 25 to 40, 25 to 35, 25 to 30, 30 to 100, 30 to 80, 30 to 70, 30 to 60, 30 to 50, 30 to 40, or 30 to 35 microns. For example, the hardened or jet-milled CE microbeads can have a particle size based on D50 volume of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100 microns.

[0212] As used herein, the term "D50 volume-based" means that 50% of the beads, by volume, have a maximum dimension less than or equal to the noted value (e.g., 10 microns). The D50 value can also be considered the median particle size. To ensure that a representative D50 value is obtained, the sample size of the beads should be at least 0.5 grams. The sample size of the microbeads is then dispersed and mixed in 1.5 ounces of isopropyl alcohol or an aqueous surfactant solution (1 drop of 5% v / v CO-630 surfactant). The D50 is tested by laser diffraction and a computer algorithm using the Mie theory for generating particle size distribution. A suitable particle size analyzer for determining the D50 value is the Malvern Mastersizer 3000 from Malvern Panalytical. When using the Malvern Mastersizer, the obscuration can be set between 2% and 5%, and the sample measurement time for both red and blue light measurements is set to three seconds. The dispersed sample is added until the desired obscuration is achieved (approximately 4%), and then the measurement is taken. After the first measurement, the sample is sonicated at 50% power for 120 seconds. Subsequently, after sonication, once the light energy is stable (usually less than one minute), the dispersed sample is measured again.

[0213] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a particle size based on D10 volume of 0.5 to 20, 0.5 to 15, 0.5 to 12, 0.5 to 10, 0.5 to 5, 0.5 to 4, 0.5 to 3, 0.5 to 2, 0.5 to 1, 1 to 20, 1 to 15, 1 to 12, 1 to 5, 1 to 3, 2 to 20, 2 to 10, 2 to 5, 3 to 20, 3 to 15, 3 to 10, 4 to 20, 4 to 15, 4 to 10, 5 to 20, 5 to 15, 5 to 10, 10 to 20, or 10 to 15 microns. For example, the hardened or jet-milled CE microbeads can have a particle size based on D10 volume of 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 microns.

[0214] As used herein, the term "based on D10 volume" means that 10% of the beads, by volume, have a maximum dimension less than or equal to the noted value (e.g., 10 microns). To ensure that a representative D10 value is obtained, the sample size of the beads should be at least 0.5 grams. The sample size of the beads is then dispersed and mixed in 1.5 ounces of isopropyl alcohol or an aqueous surfactant solution (1 drop of 5% v / v CO-630 surfactant). The D10 test is performed by laser diffraction and a computer algorithm using the Mie theory for generating particle size distribution. A suitable particle size analyzer for determining the D10 value is the Malvern Mastersizer 3000 from Malvern Panalytical. When using the Malvern Mastersizer, the obscuration can be set between 2% and 5%, and the sample measurement time for both red and blue light measurements is set to three seconds. The dispersed sample is added until the desired obscuration is achieved (approximately 4%), and then the measurement is taken. After the first measurement, the sample is sonicated at 50% power for 120 seconds. Subsequently, after sonication, once the light energy is stable (usually less than a minute), the dispersed sample is measured again.

[0215] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a particle size in the range of 1 to 100, 1 to 80, 1 to 70, 1 to 60, 1 to 50, 1 to 40, 1 to 35, 1 to 30, 1 to 25, 1 to 20, 1 to 15, 1 to 10, 5 to 100, 5 to 80, 5 to 70, 5 to 60, 5 to 50, 5 to 40, 5 to 35, 5 to 30, 5 to 25, 5 to 20, 5 to 15, 5 to 10, 10 to 100, 10 to 80, 10 to 70, 10 to 60, 10 to 50, 10 to 40, 10 to 35, 10 to 30, 10 to 25, 10 to 20, 10 to 15 30-100, 30-80, 30-70, 30-60, 30-50, 30-40, 30-35, 25-30, 30-100, 30-80, 30-70, 30-60, 30-50, 30-40, 30-35, 25-30, 30-100, 30-80, 30-70, 30-60, 30-50, 30-40, 30-35, 25-30, 30-100, 30-80, 30-70, 30-60, 30-50, 30-40, or 30-35 microns in size based on D90 volume. For example, the hardened or jet-milled CE microbeads can have a particle size based on D90 volume of 100, 90, 80, 70, 60, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, or 20 microns.

[0216] As used herein, the term "D90 volume-based" means that 90% of the beads, by volume, have a maximum dimension less than or equal to the noted value (e.g., 10 microns). To ensure that a representative D90 value is obtained, the sample size of the beads should be at least 0.5 grams. The sample size of the beads is then dispersed and mixed in 1.5 ounces of isopropyl alcohol or an aqueous surfactant solution (1 drop of 5% v / v CO-630 surfactant). The D90 is tested by laser diffraction and a computer algorithm using the Mie theory for generating particle size distribution. A suitable particle size analyzer for determining the D90 value is the Malvern Mastersizer 3000 from Malvern Panalytical. When using the Malvern Mastersizer, the obscuration can be set between 2% and 5%, and the sample measurement time for both red and blue light measurements is set to three seconds. The dispersed sample is added until the desired obscuration is achieved (approximately 4%), and then the measurement is taken. After the first measurement, the sample is sonicated at 50% power for 120 seconds. Subsequently, after sonication, once the light energy is stable (usually less than a minute), the dispersed sample is measured again.

[0217] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a particle size in the range of 1 to 100, 1 to 80, 1 to 70, 1 to 60, 1 to 50, 1 to 40, 1 to 35, 1 to 30, 1 to 25, 1 to 20, 1 to 15, 1 to 10, 5 to 100, 5 to 80, 5 to 70, 5 to 60, 5 to 50, 5 to 40, 5 to 35, 5 to 30, 5 to 25, 5 to 20, 5 to 15, 5 to 10, 10 to 100, 10 to 80, 10 to 70, 10 to 60, 10 to 50, 10 to 40, 10 to 35, 10 to 30, 10 to 25, 10 to 20, 10 to 15 30-100, 30-80, 30-70, 30-60, 30-50, 30-40, 30-35, 25-30, 30-100, 30-80, 30-70, 30-60, 30-50, 30-40, 30-35, 25-30, 30-100, 30-80, 30-70, 30-60, 30-50, 30-40, or 30-35 microns in size based on D100 volume. For example, the hardened or jet-milled CE microbeads can have a particle size based on D100 volume of 100, 90, 80, 70, 60, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, or 20 microns.

[0218] As used herein, the term "based on D100 volume" means that 100% of the beads, by volume, have a maximum dimension less than or equal to the noted value (e.g., 10 microns). To ensure that a representative D100 value is obtained, the sample size of the beads should be at least 0.5 grams. The sample size of the beads is then dispersed and mixed in 1.5 ounces of isopropyl alcohol or an aqueous surfactant solution (1 drop of 5% v / v CO-630 surfactant). The test of D100 is performed by laser diffraction and computer algorithms using the Mie theory for generating particle size distribution. A suitable particle size analyzer for determining D100 values ​​is the Malvern Mastersizer 3000 from Malvern Panalytical. When using the Malvern Mastersizer, the obscuration can be set between 2% and 5%, and the sample measurement time for both red and blue light measurements is set to three seconds. The dispersed sample is added until the desired obscuration is achieved (about 4%), and then the measurement is taken. After the first measurement, the sample is ultrasonically treated for 120 seconds at 50% power. Subsequently, after ultrasonic treatment, once the light energy is stable (usually less than one minute), the dispersed sample is measured again.

[0219] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have at least 10%, or at least 20%, or at least 30%, or at least 40%, or at least 50%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95%, or at least 96%, or at least 97%, or at least 98%, or 20% to 100%, or 20% to 90%, or 20% to 80%, or 20% to 70%, or 20% to 60%, or 30% to 100%, or 30% to 90%, or or 70% to 60%, or 70% to 100%, or 70% to 90%, or 70% to 80%, or 80% to 100%, or 80% to 90%, or 90% to 100%, or 80% to 90%, or 80% to 70%, or 80% to 100%, or 80% to 90%, or 90% to 100% average sphericity. Additionally or in the alternative, the hardened or jet-milled CE microbeads may have an average sphericity of no more than 99%, 95%, 90%, 80%, 70%, 60%, 50%, 40%, or 30%.

[0220] The average sphericity is determined by: (1) obtaining a secondary emission / ETD detector scanning electron microscopy (SEM) image of a representative sample of at least 40 microbeads, (2) on the SEM image, selecting a square sample window centered on the center of the SEM that contains exactly 30 microbeads with the entire outer perimeter of the microbead clearly visible (i.e., not obscured), (3) measuring the maximum and minimum diameters of the 30 clearly visible microbeads in the sample window (each diameter extends through the center of mass of the particle and is not necessarily perpendicular to each other), (4) for each of the 30 particles, dividing the minimum diameter by the maximum diameter and multiplying the result by 100% to obtain the sphericity of 30 individual particles, and (5) averaging the sphericity of the 30 individual particles to obtain the average sphericity.

[0221] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads exhibit a unimodal particle size distribution having a span of at least 0.5, at least 0.55, at least 0.60, at least 0.65, at least 0.70, at least 0.75, at least 0.80, at least 0.85, at least 0.9, at least 0.95, at least 1.0, at least 1.05, at least 1.1, at least 1.15, at least 1.2, or at least 1.25. In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads exhibit a unimodal particle size distribution with a span of at least 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, or 1.4, and / or less than 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, or 1.5. In certain embodiments, the hardened or jet-milled CE microbeads exhibit a unimodal particle size distribution with a span of 1.0 to 3.0, 1.0 to 2.5, 1.0 to 2.0, 1.0 to 1.8, 1.0 to 1.6, 1.2 to 3.0, 1.2 to 2.5, 1.2 to 2.0, 1.2 to 1.8, 1.2 to 1.6, 1.3 to 3.0, 1.3 to 2.5, 1.3 to 2.0, 1.3 to 1.8, or 1.3 to 1.6. As used herein, "unimodal particle size distribution" refers to a particle size distribution of a material having only a single significant size distribution peak. This is in contrast to a multimodal particle size distribution, which has two or more particle size distribution peaks. The "span" of a unimodal peak can be measured using the D10, D50, and D90 values ​​of the particles using the following formula:

[0222] (D x (90)-D x (10)) / Dx (50),

[0223] Where "x" is the specified particle size.

[0224] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have an average smoothness of at least 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 95%, 97%, 98% or 99%. In addition or in the alternative, the hardened CE or jet-milled microbeads may have an average smoothness of no more than 99%, 95%, 90%, 80%, 70%, 60%, 50%, 40% or 30%.

[0225] The average smoothness was determined by: (1) acquiring a secondary emission / EDT detector scanning electron microscopy (SEM) image of a representative sample of at least 20 microbeads, (2) on the SEM, selecting a square sample window centered at the center of the SEM that contained exactly 10 microbeads with the entire outer perimeter of the microbead clearly visible (i.e., not obscured), (3) binarizing the sample window by manual binarization, selecting upper and lower thresholds to match the exact shape of the darker regions of the particles, (4) for each of the 10 microbeads, selecting a square window at or near the center of the particle with a length and width of approximately 1 / 3 of the particle diameter (before binarizing the particle), (5) dividing the area of ​​the dark region in the square window by the total area of ​​the square window and multiplying the result by 100% to obtain the smoothness of the 10 individual particles, and (5) averaging the 10 individual particle smoothnesses to obtain the average smoothness.

[0226] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet milled CE microbeads have a particle size of at least 0.1, 0.5, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5 .2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9 or 8.0m2 / g, and / or not more than 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2.5, 2, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4 or 1.3m 2 The average BET surface area of ​​​​the sample is 2.5477 square meters.

[0227] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a BET average pore size of at least 25, 30, 35, 40, 45, 50, 55, 56, 57, 58 or 59 angstroms, and / or less than 75, 70, 65 or 60 angstroms, measured according to ISO 9277 and ISO 15901-02 using a Micromeritics ASAP 2020 instrument and nitrogen gas.

[0228] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a BJH average pore size of at least 50, 60, 70, 80, 90, 100, 110, 120, 125 or 130 angstroms, and / or less than 200, 190, 180, 170, 160, 150, 140 or 130 angstroms, measured according to ISO 15901-02 using a Micromeritics ASAP 2020 instrument and nitrogen gas.

[0229] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a particle size of at least 0.5, 1.0, 1.1, 1.2, 1.3, 1.4, or 1.5, and / or less than 2.5, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, or 1.3 m / s as measured according to ISO 15901-02 using a Micromeritics ASAP 2020 instrument and nitrogen gas. 2 / g of BJH surface area of ​​pores ranging from 17 to 3,000 angstroms.

[0230] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a BJH volume of pores from 17 to 3,000 angstroms of at least 0.001, 0.002, 0.003, or 0.004, and / or less than 0.1, 0.05, or 0.01 mL / g, measured according to ISO 15901-02 using a Micromeritics ASAP 2020 instrument and nitrogen gas.

[0231] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a true specific gravity of at least 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, and / or no more than 1.5, 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7 or 0.6 as measured by JIS Z8807-1976.

[0232] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a bulk specific gravity of at least 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, and / or no more than 1.4, 1.3, 1.2, 1.1, 1.0, 0.9, 0.8, 0.7, 0.6 or 0.5 as measured by JIS 1201-1.

[0233] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a polydispersity index of less than 0.8, 0.7, 0.6, 0.5, 0.4 or 0.3.

[0234] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a surfactant content of less than 200, 150, 100, 50, 20, 10, 7.5, 5, 2.5 or 1 ppmw.

[0235] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a plasticizer content of less than 200, 150, 100, 50, 20, 10, 7.5, 5, 2.5 or 1 ppmw.

[0236] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a butyric acid content of less than 500, 400, 300, 200, 100, 50, 20, 10, 7.5, 5, 2.5 or 1 ppmw.

[0237] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have an acetic acid content of less than 500, 400, 300, 200, 100, 50, 20, 10, 7.5, 5, 2.5 or 1 ppmw.

[0238] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a propionic acid content of less than 500, 400, 300, 200, 100, 50, 20, 10, 7.5, 5, 2.5 or 1 ppmw.

[0239] The butyric acid, acetic acid and propionic acid content of hardened or jet-milled CE microbeads can be measured by gas chromatography ("GC"). Under one GC method, the content of butyric acid, acetic acid and propionic acid can be measured by adding about 100 mg of hardened or jet-milled CE microbeads to a vial that has been tared to 4 dram, followed by the addition of an internal standard solution containing nonane in a mixture of 90:10 dichloromethane / methanol. A magnetic stirring bar is placed in the vial and the sample is stirred for two hours. After stirring, 8.0 mL of n-heptane is added dropwise to precipitate the polymer, and the sample is then vortexed. About 100 mg of supernatant is transferred to a GC vial with 100 μL of pyridine and 450 μL of BSTFA. The sample is heated at 80°C for 30 minutes and then cooled to room temperature before injection. The sample is chromatographed on a 100% dimethylpolysiloxane and 14% cyanopropyl-phenyl-methylpolysiloxane column using a programmed temperature method and flame ionization detection. Alternatively, the second GC method involves preparing the sample by adding about 30 mg of hardened or jet-milled CE beads to a tared GC vial, followed by the addition of 200 μL of an internal standard solution containing decane in pyridine and 1.0 mL of BSTFA. The vial is heated at 80°C for 30 minutes and then cooled to room temperature before injection. The sample is then chromatographed on a 100% dimethylpolysiloxane and 6% cyanopropyl-phenyl-methylpolysiloxane column using a programmed temperature method and flame ionization detection.

[0240] In one embodiment or in combination with any embodiment mentioned herein, the hardened or jet-milled CE microbeads have a sulfuric acid content of less than 500, 400, 300, 200, 100, 50, 20, 10, 7.5, 5, 2.5 or 1 ppmw. The sulfuric acid content of the hardened or jet-milled CE microbeads can be measured by the following method. First, the tested sample is added to the titration cell and dissolved in a solvent to reach a total volume of 70 mL. For comparison, a solvent blank is also prepared. Then an automatic titrator equipped with a combined glass potentiometric electrode is used to titrate the sample and blank with 0.05N potassium hydroxide in methanol. The acid value is calculated based on the sample weight and the KOH consumed in the sample minus the KOH consumed in the blank.

[0241] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a CE content of at least 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99% by weight of the mixed cellulose ester of the first, second and / or third aspects (including any categories or subcategories of these aspects). In addition, or in the alternative, the hardened or jet-milled CE microbeads may have a CE content of less than 99.9%, 99.5%, 99%, 98%, 97%, 96%, 95%, 94%, 93%, 92%, 91%, 90%, 89%, 88%, 87%, 86%, or 85% by weight of the mixed cellulose esters of the first, second, and / or third aspects, including any classes or subclasses of these aspects. In certain embodiments, the hardened or jet-milled CE microbeads may consist essentially of the mixed cellulose esters of the first, second, and / or third aspects, including any classes or subclasses of these aspects.

[0242] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads may contain a biodegradable additional cellulose ester different from the mixed cellulose ester of the first, second and / or third aspects. In such embodiments, this additional cellulose ester may be cellulose acetate, which exhibits at least 40% biodegradability, at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C or OECD 301F test methods.

[0243] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads may contain at least 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt% of additional biodegradable cellulose esters different from the mixed cellulose esters of the first, second, and / or third aspects. Additionally, or in the alternative, the hardened or jet-milled CE microbeads may contain less than 50 wt%, 45 wt%, 40 wt%, 35 wt%, 30 wt%, 25 wt%, 20 wt%, 15 wt%, 10 wt%, or 5 wt% of additional biodegradable cellulose esters different from the mixed cellulose esters of the first, second, and / or third aspects.

[0244] In one embodiment or in combination with any of the embodiments mentioned herein, the hardened or jet-milled CE microbeads have a moisture content of one or more of the following amounts: (1) greater than 0 wt %; (2) no more than 10 wt %, 9 wt %, 8 wt %, 7 wt %, 6 wt %, 5 wt %, 4 wt %, 3 wt %, 2 wt %, 1 wt % or 0.05 wt %; and (3) in the range of 0-10 wt %, 0-5 wt %, 0-4 wt %, 0-3 wt %, or 1.3 wt %.

[0245] In one embodiment or in combination with any other embodiment mentioned herein, the hardened or jet-milled CE microbeads exhibit at least 40% biodegradability, at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 56 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0246] In one embodiment or in combination with any other embodiment mentioned herein, the hardened or jet-milled CE microbeads exhibit at least 40% biodegradability, at least 45% biodegradability, or at least 50% biodegradability, or at least 55% biodegradability, at least 60% biodegradability, or at least 65% biodegradability, or at least 70% biodegradability, or at least 75% biodegradability, or at least 80% biodegradability, or at least 85% biodegradability, or at least 90% biodegradability, or at least 95% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

[0247] In one embodiment or in combination with any other embodiment mentioned herein, the hardened or jet-milled CE microbeads exhibit an oil absorption of at least 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 milliliters per 100 grams measured using test method ASTM D281, wherein mineral oil is used in place of castor oil.

[0248] In one embodiment or in combination with any other embodiment mentioned herein, the hardened or jet-milled CE microbeads exhibit a zeta potential of at least -95, at least -90, at least -85, at least -80, at least -75, at least -70, at least -65, at least -60, at least -55, at least -50, or at least -45 mV. In addition, or in the alternative, the hardened or jet-milled CE microbeads may exhibit a zeta potential of less than -5, less than -10, less than -15, less than -20, less than -25, less than -30, less than -35, less than -40, less than -45, less than -50, less than -55, less than -60, or less than -65 mV.

[0249] Zeta potential was measured by dispersing the beads in water for 30 seconds via vortex mixing. The bead concentration was controlled at 0.5 mg / ml. Zeta potential measurements were performed on a ZetasizerNano series ZEN 3600 instrument from Malvern Panalytical equipped with a DTS1070 sample cell. Zeta potential calculations were then performed using the Smoluchowski model.

[0250] In one embodiment or in combination with any other embodiment mentioned herein, the hardened or jet-milled CE microbeads exhibit a haze transmittance of at least 10%, at least 15%, at least 20%, at least 25%, at least 30%, at least 35%, at least 40%, or at least 45%. In addition, or in the alternative, the hardened or jet-milled CE microbeads may exhibit a haze transmittance of less than 90%, or less than 85%, or less than 80%, or less than 75%, or less than 70%, or less than 65%, or less than 60%, or less than 55%, or less than 50%, or less than 45%, or less than 40%, or less than 35%, or less than 32%, or less than 30%. The haze transmittance can be measured using a BYK gloss meter and BYK Haze Gard I by forming an aqueous emulsion containing 5 wt% or 7 wt% of the biodegradable beads.

[0251] The detailed procedure for measuring haze is as follows. The W / O emulsion for measuring haze % is prepared using the following procedure. Two phases are used to prepare the emulsion. Phase A is made of water, magnesium sulfate heptahydrate (Merck) and Euxyl PE9010 (Ashland) at the following weight concentrations of 59:2:1 respectively. Phase B is prepared by caprylic / capric triglyceride (Making Cosmertics), C1215 alkyl benzoate (Making Cosmeti cs), Emullium Illustro (Gattefosse), bentone Gel ISD V (Elementis), and microbead powder at the following weight concentrations of 12.5:12.5:5:3:5 respectively. Phase A is prepared by mixing the listed components. Phase B is prepared by top stirring until all components are dissolved in the absence of microbead powder. Phase A is then added to phase B while stirring at 1000rpm until fully mixed. Microbead powder is then added to the mixture while mixing at 1000rpm for 5 minutes. The resulting mixture was homogenized with an Ultra Turax at 10,000 rpm for 5 minutes. The haze transmittance of the calendered film (38 um) after drying at 50°C for 5 minutes was measured using BYK Haze Gard I.

[0252] In one embodiment or in combination with any other embodiment mentioned herein, the hardened or jet-milled CE microbeads exhibit a total transmittance of at least 50%, at least 60%, at least 70%, at least 75%, at least 80%, at least 85%, at least 86%, at least 87%, at least 88% or at least 89% measured using a BYK Haze-Gard I unit.

[0253] Cosmetic preparations

[0254] The hardened or jet-milled CE microbeads produced by the methods disclosed herein can be used to produce various cosmetic compositions. The cosmetic composition can be produced by: (1) providing a plurality of hardened or jet-milled CE microbeads; (2) combining the hardened or jet-milled CE microbeads with one or more cosmetic additives to form a pre-cosmetic mixture; and (3) forming a cosmetic composition from the pre-cosmetic mixture.

[0255] In one embodiment or in combination with any other embodiment, the present application discloses a cosmetic composition comprising any of the CE microbeads disclosed herein (hardened or jet-milled).

[0256] In one embodiment or in combination with any other embodiment mentioned herein, the cosmetic composition may comprise at least 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt% of hardened or jet-milled CE microbeads. In addition, or in the alternative, the cosmetic composition may comprise less than 99 wt%, 90 wt%, 80 wt%, 70 wt%, 60 wt%, 50 wt%, 40 wt%, 30 wt%, 25 wt%, 20 wt%, 15 wt%, 10 wt%, or 5 wt% of hardened or jet-milled CE microbeads. For example, the cosmetic composition may include 0.1 wt % to 90 wt %, 0.1 wt % to 50 wt %, 0.1 wt % to 30 wt %, 0.1 wt % to 20 wt %, 0.1 wt % to 15 wt %, 0.1 wt % to 10 wt %, 0.1 wt % to 5 wt %, 1 wt % to 90 wt %, 1 wt % to 50 wt %, 1 wt % to 30 wt %, 1 wt % to 20 wt %, 1 wt % to 15 wt %, 1 wt % to 10 wt %, or 1 wt % to 5 wt % of hardened or jet-milled CE microbeads.

[0257] In one embodiment or in combination with any other embodiment mentioned herein, the cosmetic composition can be a foundation, a sunscreen, a lipstick, a mascara, an eye shadow, a lotion, a dry shampoo, a liquid shampoo, a body wash, a lotion, a hair conditioner, a skin moisturizer, a face cleanser, a tablet, a foot powder, a baby powder, a shaving cream, or a shaving gel.

[0258] In one embodiment or in combination with any other embodiment mentioned herein, the cosmetic composition may be a loose powder, a pressed powder, a gel, an emulsion, a liquid, or an aerosol.

[0259] In one embodiment or in combination with any other embodiment mentioned herein, the cosmetic composition comprises at least 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 99% by weight of at least one, two, three, four, or five cosmetic additives. In addition, or in the alternative, the cosmetic composition may comprise less than 99%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, or 50% by weight of at least one, two, three, four, or five cosmetic additives. For example, the cosmetic composition may contain 1 wt % to 99 wt %, 1 wt % to 95 wt %, 1 wt % to 90 wt %, 1 wt % to 85 wt %, 1 wt % to 80 wt %, 5 wt % to 99 wt %, 5 wt % to 95 wt %, 5 wt % to 90 wt %, 5 wt % to 85 wt %, 10 wt % to 99 wt %, 10 wt % to 95 wt %, 10 wt % to 85 wt %, 10 wt % to 80 wt %, 15 wt % to 99 wt %, 15 wt % to 95 wt %, 15 wt % to 90 wt %, 15 wt % to 85 wt %, or 15 wt % to 80 wt % of at least one, two, three, four, or five cosmetic additives.

[0260] Generally speaking, cosmetic additives may include solvents, colorants, oils, waxes, fatty acids, alcohols, esters, hydrocarbons, silicone oils, surfactants, metal soaps, moisturizers, thickeners, UV absorbers, antioxidants, oil absorbers, exfoliants, water, or combinations thereof.

[0261] In one embodiment or in combination with any other embodiment mentioned herein, the colorant comprises a pigment (eg, an organic pigment and / or an inorganic pigment) and / or a dye.

[0262] In one embodiment or in combination with any other embodiment mentioned herein, the oil comprises triglycine, soybean oil, cocoa butter, palm oil, palm kernel oil, hardened oil and / or hardened castor oil.

[0263] In one embodiment or in combination with any other embodiments mentioned herein, the wax comprises carnaubawax, candelilla, lanolin, lanolin, candelilla wax, cotton wax, montan wax, kapok wax, lanolin acetate, lanolin and / or lanolin fatty acid isopropyl ester.

[0264] In one embodiment or in combination with any other embodiments mentioned herein, the fatty acid comprises lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, behenic acid, oleic acid, undecylenic acid, linoleic acid, eicosapentaenoic acid (EPA) and / or docosahexaenoic acid.

[0265] In one embodiment or in combination with any other embodiments mentioned herein, the alcohol comprises cetyl alcohol, stearyl alcohol, isostearyl alcohol, 2-octyldodecanol, lauryl alcohol, behenyl alcohol, myristyl alcohol, oleyl alcohol, and / or cetearyl alcohol.

[0266] In one embodiment or in combination with any other embodiment mentioned herein, the esters include isopropyl myristate, 2-octyldodecyl myristate, cetyl 2-ethylhexanoate, diisostearyl malate, tripropylene glycol dipivalate, isononyl isononanoate, isotridecyl isononanoate, isotoridecyl isononanoate, isononanoate), cetyl octanoate, isocetyl palmitate, butyl stearate, hexyl laurate, myristyl myristate, decyl oleate, hexyl decyl dimethyl octanoate, cetyl lactate, myristyl lactate, lanolin acetate, isocetyl stearate, isocetyl isostearate, cholesterol 12-hydroxystearate, ethylene glycol di-2-ethylhexanoate, dipentaerythritol fatty acid ester, N-alkyl glycol monoisostearate, neopentyl glycol dicaprate, di-2-heptyl undecanoate glyceryl, trimethyl propane tri-2-ethylhexanoate, triisostearate trimethylolpropane triol ester, pentaerythritol tetra-2-ethylhexanoate, tri-2-ethylhexanoin, tricaprylin, triisopalmitin, trimethylolpropane triisostearate, ethylhexyl palmitate, trimyristin, tri-2-heptylundecanoic acid glyceryl, castor oil fatty acid methyl ester, oleyl oleate, acetylated glycerol, 2-heptylundecanoic acid, diisobutyl adipate, hexyldecyl palmitate N-lauroyl-L-glutamate, hexyldecyl adipate, diisopropyl sebacate, ethylhexyl succinate and / or triethyl citrate.

[0267] In one embodiment or in combination with any other embodiments mentioned herein, the hydrocarbon comprises paraffin, petrolatum, and / or microcrystalline wax.

[0268] In one embodiment or in combination with any other embodiment mentioned herein, the surfactant comprises an anionic surfactant, a cationic surfactant and / or a nonionic surfactant.

[0269] In one embodiment or in combination with any other embodiment mentioned herein, the thickening agent comprises guar gum, pectin, starch, gelatin, collagen, cellulose derivatives and / or mannan.

[0270] Example

[0271] abbreviation

[0272] CAB is cellulose acetate butyrate; DSOH is the average degree of substitution of hydroxyl substituents; DSAc is the average degree of substitution of acetyl substituents; DSBu is the average degree of substitution of butyryl substituents; PS denotes D(4,3) particle size.

[0273] CE coatings were prepared as shown in Table 3 below to determine the solubility of CE (such as cellulose acetate butyrate (CAB), Example 1) in a solvent system containing ethyl acetate (EA), n-propanol (nPrOH) and water. The preparation of Example 1 is shown below.

[0274] Example 1: Cellulose acetate butyrate (DS Ac =1.87,DS Bu =0.22,DS OH =0.91M w =90766)

[0275] A mixture of cellulose and acid [cellulose (4.3 parts) and AcOH (11.8 parts)] was added to a stirred reactor and then soaked without heating, and the mixture was heated to 55° C. Sulfuric acid was added and the reaction mixture was cooled to 30° C. Subsequently, Ac2O (8.9 parts) and Bu 2O A mixture of (5.6 parts) of 1,2-dihydro-1,4 ...

[0276] General Procedure for the Preparation of Cellulose Esters

[0277] The cellulose mixture [cellulose and AcOH] ("cellulose mixture") and sulfuric acid, Ac2O and Bu2O ("acylation solution") were cooled to 30°C in a stirred reactor, and the reaction mixture was cooled to about 7°C under stirring. Additional sulfuric acid was added to the target amount, and the resulting reaction mixture was warmed to 45°C-65°C under stirring until the reagents were consumed. The reaction mixture was treated with an aqueous solution of AcOH and BuOH ("hydrolysis solution") and stirred at 68°C under hydrolysis conditions. The reaction mixture was then quenched, neutralized, precipitated, washed and dried by conventional methods.

[0278] Examples 2-5 were prepared by employing the general procedure for preparing cellulose esters using the reagents and conditions shown in Table 1. Table 2 provides the various degrees of substitution and molecular weights for Examples 2-5.

[0279] Table 1.

[0280]

[0281] Table 2.

[0282] Example Degree of substitution MW 2 <![CDATA[DS OH =0.6,DS Bu =0.21,DS Ac =2.19]]> 109K 3 <![CDATA[DS OH =0.7,DS Bu =0.21,DS Ac =2.08]]> 68.3K 4 <![CDATA[DS OH =0.8,DS Bu =0.2,DS Ac =1.99]]> 72.2K 5 <![CDATA[DS OH =0.9,DS Bu =0.2,DS Ac =1.86]]> 78,2

[0283] Degree of substitution

[0284] The degree of substitution of the substituents on the main chain of cellulose esters was calculated using proton nuclear magnetic resonance spectroscopy. Gel permeation chromatography was performed on cellulose esters in stabilized tetrahydrofuran. The instrument was an Agilent 1260, which consisted of a degasser, an isocratic pump with a flow rate of 1.0 ml / min, an autosampler with an injection volume of 25 microliters, a column oven set at 28°C, and a refractive index detector at 28°C. The column set consisted of an Agilent PLgel 5 micron guard column, Mixed-C, and Oligopore in series. The system was calibrated with monodisperse polystyrene standards with a molecular weight range of about 4 million to 162. The sample was prepared as follows: about 25 mg of sample was weighed in 10 ml of solvent with the addition of 10 microliters of toluene to be used as a flow rate marker, a stirring bar was added to an 8-dollar screw cap vial, and stirred until dissolved.

[0285] Molecular weight

[0286] Molecular weight is determined by gel permeation chromatography. Gel permeation chromatography is performed on cellulose esters in stabilized tetrahydrofuran. The instrument is an Agilent 1260, which consists of a degasser, an isocratic pump with a flow rate of 1.0 ml / min, an autosampler with an injection volume of 25 microliters, a column oven set at 28°C, and a refractive index detector at 28°C. The column set consists of an Agilent PLgel 5 micron guard column, Mixed-C, and Oligopore in series. The system is calibrated with monodisperse polystyrene standards with a molecular weight range of about 4 million to 162. The sample is prepared as follows: weigh about 25 mg of sample in 10 ml of solvent with the addition of 10 microliters of toluene to be used as a flow rate marker, add a stirring bar to an 8-dollar screw cap vial, and stir until dissolved.

[0287] Preparation of CE coatings

[0288] The CE coatings were prepared by charging the corresponding amount of solvent system into a dry 250 mL one-neck round bottom flask equipped with a magnetic stirrer. The solvent system was stirred and then the corresponding amount / type of CAB was charged into the flask. The CAB was charged into the flask in the following manner: the solids were slowly metered at a certain rate so that the stirring vortex could move the solid particles into the solvent system without forming large pieces of powder on top of the liquid phase. This mixture of solvent and CAB was stirred at room temperature for 45 minutes. If the mixture became homogeneous within this time period, the coating was determined to be "soluble". If the solid particles were still not dissolved in the solvent system at 60 minutes, the coating was determined to be "insoluble".

[0289] In coatings 1-1, 1-2, and 1-3, the solvent system contained different amounts of ethyl acetate and n-propanol, but no water. In coatings 1-1a, 1-2a, and 1-3a, water was added to the solvent system. That is, the solvent systems of coatings 1-1 and 1-1a, 1-2 and 1-2a, and 1-3 and 1-3a contained the same amounts of ethyl acetate and n-propanol, and the only difference between the respective coatings was the addition of water.

[0290] In coating 1-4a, the amount of CAB contained in the CE coating was increased to match the mass % CAB of the coatings without water (ie, coatings 1-1, 1-2, and 1-3).

[0291] Table 3.

[0292]

[0293] It is noteworthy that the CE coatings without water were unable to dissolve the CE contained therein. For example, coating 1-1 provided a lumpy and inhomogeneous mixture, and coatings 1-2 and 1-3 provided initially stirrable slurries but became lumpy and inhomogeneous after a few minutes.

[0294] In contrast, coating 1-1a provided a stirrable slurry rather than a clumpy slurry. Coatings 1-2a and 1-3a provided a homogeneous mixture in which the CE dissolved in the solvent system within 3 minutes.

[0295] As shown in coating 1-4a, increasing the mass of CE contained in the CE coating also provided a homogenous mixture in which the CE dissolved in the solvent system within 3 minutes. That is, increasing the % CAB of the CE coating did not appear to negatively affect the solubility of CE in the solvent system.

[0296] Emulsion method for preparing microparticles

[0297] Prepare a clean, dry 3-liter kettle flask (with baffles) equipped with a two-layer overhead mechanical agitator and a bottom drip valve. Charge the kettle with 700-1,300 g of deionized water, 6-13 g of Tergitol 15-S-40, and 0-1.0 g of PEG-100 stearate. Add 7-12 g of a colloidal protective agent (low, medium, or high viscosity carboxymethyl cellulose or methyl cellulose) to the stirred aqueous mixture over 15 minutes. Allow the mixture to stir at ambient temperature for one hour or until homogeneous.

[0298] Prepare a separate clean, dry 2-liter kettle flask equipped with an overhead mechanical stirrer and a bottom drip valve. Prepare a coating solution consisting of 10-100% cellulose ester using 0-5.0 parts of C1-C4 alkyl acetate, 0-1.0 parts of C1-C3 alcohol, and 0-0.80 parts of deionized water (based on the mass of cellulose ester used). Allow the mixture to stir at ambient temperature until homogeneous.

[0299] The coating solution was added to a 3 liter kettle over 30 minutes with vigorous stirring (250-500 rpm). After the addition was complete, the emulsion was circulated at 100-300 ml / min through a flow cell containing a high shear mixer (0-12,000 rpm) for 45-60 minutes.

[0300] After the high shear mixing time is complete, the emulsion is pumped at 300 mL / min into a 5-gallon bucket equipped with a single-layer overhead mechanical agitator containing 4000-6000 g of deionized water and agitated at 250-500 rpm for 0-16 hours. After the hold time, centrifugation is performed to separate the spherical particles. The particles are suspended in 1-2 L of deionized water and centrifuged again. This washing process is repeated once.

[0301] The microparticles were placed in a mixer with a sigma blade and dried under vacuum (100-400 mmHg) at 50-100°C for 16 hours. Typical recovery yields were 75-85%.

[0302] Jet milling method for preparing microparticles

[0303] There are a variety of jet milling configurations that can be used to reduce the size of particles. Such configurations are discussed in A. Chamayou and JA Dodds, Air Jet Milling, Handbook of Powder Technology, Vol. 12, Chapter 8, 2007 ("Chamayou"). Chamayou's Figure 7An example of a fluidized bed opposed jet mill is provided, which can be used to reduce the size of the cellulose ester particles described in Table 4 below. The jet milling process is used to reduce the average particle size of cellulose ester from 300-900 μm to about 10 μm. The operation of the fluidized bed opposed jet mill is as follows: the cellulose ester is placed in a hopper and is usually introduced into the top of the mill ("FEED IN") through a double valve arrangement (or by a syringe). The cellulose ester particles fall to the bottom of the mill under gravity, where they are drawn into one of three high-pressure air flows that are geometrically oriented toward each other, thereby forming a so-called "crushing zone". In the crushing zone, the size of the cellulose ester particles is reduced via collisions between particles. The reduced-size particles are then transported upward by mass transfer in the vertical air flow (fluidized bed), thereby ultimately bringing them into a classifier. The classifier enables particles below the required minimum size to be removed from the grinder ("FINE OUT"). Particles exceeding the maximum size are rejected from the classifier and sent back to the fluidized bed to eventually fall back into the comminution zone for further size reduction. Particles falling within the desired size range are ejected from the classifier into an appropriate product container. There are many control parameters for optimizing production rate, particle size, and particle size distribution shape, including but not necessarily limited to classifier rotor speed, air nozzle pressure, and bed level.

[0304] Table 4.

[0305]

[0306] OECD 301F Test Description

[0307] In this experiment, a measured volume of mineral culture medium is inoculated with a known concentration of the test substance, which serves as a nominal source of organic carbon. The medium is placed in a closed flask and stirred at a constant temperature (within +1°C or closer) for up to 60 days.

[0308] Oxygen consumption can be determined using one of two methods: either by measuring the amount of oxygen required to maintain a constant amount of gas in the respirometer flask (generated electrolytically), or by monitoring changes in volume or pressure (or a combination of both) in the instrument.

[0309] Any carbon dioxide produced during the process is absorbed using potassium hydroxide solution or another suitable absorbent. The amount of oxygen utilized by the microbial population during biodegradation of the test substance is calculated by subtracting the oxygen uptake of a blank inoculum (performed in parallel). This value is expressed as a percentage of the theoretical oxygen demand (ThOD) or, less ideally, the chemical oxygen demand (COD).

[0310] Haze measurement

[0311] The haze percentage of the formulation is measured using the BYKhaze gard. The instrument haze gard produces a light beam that shines on the sample, where a portion of the light is transmitted and enters an integrating sphere that measures the transmitted haze. It uses unidirectional illumination and diffuse observation.

[0312] Haze Measurement Procedure

[0313] Clean the Gorilla Glass using acetone or ethanol to ensure that there are no streaks on the substrate. Use a 1.5 square mil calendering rod to calender the formulation onto the Gorilla Glass. Pull the rod from top to bottom across the substrate at a constant speed / pressure to make a uniform sample for testing. The samples should be uniform and of equal thickness. Place the samples in an oven to dry at 35-40°C for 5 minutes. Allow the samples to cool completely after removing from the oven. Place the calendered sample in front of the haze sensor for haze measurement. Take three readings on a sample at the top, middle, and bottom of the calender. Each sample is calendered 3 times. Take the average of the nine readings and report the haze percentage.

[0314] Haze of particles in a single oil dispersion

[0315] Table 5 provides the haze of various microparticles in a single oil dispersion. The dispersion was either 5 wt% or 7 wt% in dimethicone. The microparticles were thoroughly dispersed in dimethicone using a mixer.

[0316] All added microparticles showed higher haze numbers compared to the dimethicone oil base. Cellulose ester microparticles showed similar or better haze % compared to the external benchmark microparticles. By exhibiting higher haze %, it can be concluded that the cellulose ester microparticles imparted an enhanced optical effect.

[0317] Table 5.

[0318]

Claims

1. Biodegradable microparticles comprising mixed cellulose esters, wherein the biodegradable microparticles exhibit a biodegradability of at least 50% at 60 days according to at least one of the OECD 301B, OECD 301C or OECD 301F test methods and exhibit a haze transmittance of at least 10%, wherein the mixed cellulose ester comprises- (a) an average degree of substitution (DS) of acetyl substituents in the range of 0.1 to 2.3 Ac ”), (b) an average degree of substitution ("DS") of propionyl substituents in the range of 0.1 to 1.5 Pr ”) or the average degree of substitution of butyryl substituents (“DS Bu "),as well as (c) an average degree of substitution ("DS") of hydroxyl substituents in the range of 0.6 to 2.8 OH ”).

2. The biodegradable microparticle according to claim 1, wherein the biodegradable microparticle exhibits a haze transmittance of at least 15%, at least 20%, at least 25%, at least 30%, at least 35%, at least 40% or at least 45%, and / or wherein the biodegradable microparticle exhibits a haze transmittance of less than 90%, or less than 85%, or less than 80%, or less than 75%, or less than 70%, or less than 65%, or less than 60%, or less than 55%, or less than 50%, or less than 45%, or less than 40%, or less than 35%, or less than 32%, or less than 30%, measured using a BYK Haze-Gard I unit.

3. The biodegradable microparticle according to any one of claims 1-2, wherein the biodegradable microparticle exhibits a span of at least 0.5, at least 0.55, at least 0.60, at least 0.65, at least 0.70, at least 0.75, at least 0.80, at least 0.85, at least 0.9, at least 0.95, at least 1.0, at least 1.05, at least 1.1, at least 1.15, at least 1.2 or at least 1.25, and / or less than 3.0, ... or 1.2 to 2, or 1.2 to 1.8, or 1.2 to 1.6, or unimodal particle size distribution.

4. The biodegradable microparticles according to any one of claims 1 to 3, wherein the biodegradable microparticles have a particle size based on D50 volume in the range of 5 to 20, or 5 to 15, or 5 to 10, or 6 to 20, or 6 to 15, or 6 to 10, or 7 to 20, or 7 to 15, or 7 to 10, or 8 to 20, or 8 to 15, or 8 to 10, or 9 to 20, or 9 to 15, or 9 to 10, or 10 to 20, or 10 to 15 microns.

5. The biodegradable microparticle according to any one of claims 1 to 4, wherein the biodegradable microparticle exhibits a biodegradability of at least 40%, or at least 45%, or at least 50%, or at least 55%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95% at 60 days according to at least one of the OECD 301B, OECD 301C or OECD 301F test methods; and / or wherein the mixed cellulose ester exhibits a biodegradability of at least 40%, or at least 45%, or at least 50%, or at least 55%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95% at 60 days according to at least one of the OECD 301B, OECD 301C or OECD 301F test methods.

6. The biodegradable microparticle according to any one of claims 1 to 5, wherein the DS Ac is at least 0.2, at least 0.3, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 1.0, at least 1.1, at least 1.2, at least 1.3, at least 1.4, at least 1.5, at least 1.6, at least 1.7, at least 1.8, at least 1.9, or at least 2.0, or from 1.8 to 2.3, or from 1.8 to 2.2, or from 1.8 to 2.1, or from 1.8 to 2.0, or from 1.85 to 2.3, or from 1.8 to 2.2, or from 1.8 to 2.1, or from 1.8 to 2.

0.

7. The biodegradable microparticle according to any one of claims 1 to 6, wherein the DS Ac Less than 2.3, less than 2.2, less than 2.1, less than 2.0, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1.0, less than 0.9, less than 0.8, less than 0.7, less than 0.5, less than 0.4 or less than 0.

3.

8. The biodegradable microparticle according to any one of claims 1 to 7, wherein the DS Pr It is at least 0.2, or at least 0.3, or at least 0.4, or at least 0.5, at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, at least 1.2, or at least 1.3, or at least 1.

4.

9. The biodegradable microparticle according to any one of claims 1 to 8, wherein the DS Pr Less than 1.5, less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, less than 0.7, or less than 0.5, or less than 0.4, or less than 0.

3.

10. The biodegradable microparticle according to any one of claims 1 to 9, wherein the DS Bu is at least 0.2, or at least 0.3, or at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or 0.18 to 0.23, or 0.18 to 0.22, or 0.18 to 0.21, or 0.18 to 0.20, or 0.18 to 0.19, or 0.19 to 0.23, or 0.19 to 0.22, or 0.19 to 0.21, or 0.19 to 0.2, or 0.2 to 0.23, 0.2 to 0.22, or 0.2 to 0.21; and / or wherein the DS Bu Less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.9, or less than 0.8, or less than 0.7, or less than 0.5, or less than 0.4, or less than 0.

3.

11. The biodegradable microparticle according to any one of claims 1 to 10, wherein the DS OH is at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or from 0.5 to 0.95, or from 0.5 to 0.93, or from 0.5 to 0.91, or from 0.5 to 0.9, or from 0.5 to 0.85, or from 0.5 to 0.80, or from 0.5 to 0.75, or from 0.5 to 0.7, or from 0.55 to 0. 95, or 0.55 to 0.93, or 0.55 to 0.91, or 0.55 to 0.9, or 0.55 to 0.85, or 0.55 to 0.80, or 0.55 to 0.75, or 0.55 to 0.7, or 0.6 to 0.95, or 0.6 to 0.93, or 0.6 to 0.91, or 0.6 to 0.9, or 0.6 to 0.85, or 0.6 to 0.80, or 0.6 to 0.75, or 0.6 to 0.7, or 0.65 to 0.95, or 0.65 to 0.93, or 0.65 to 0.91, or 0.65 to 0.9, or 0.65 to 0.85, or 0.65 to 0.80, or 0.65 to 0.75, or 0.65 to 0.7, or 0.7 to 0.95, or 0.7 to 0.93, or 0.7 to 0.91, or 0.7 to 0.9, or 0.7 to 0.85, or 0.7 to 0.80, or 0.7 to 0.75, or 0.8 to 0.95, or 0.8 to 0.93, or 0.8 to 0.91, or 0.8 to 0.9, or 0.8 to 0.85, or 0.85 to 0.95, or 0.85 to 0.93, or 0.85 to 0.91, or 0.85 to 0.9, or 0.9 to 0.95, or 0.9 to 0.93, or 0.9 to 0.91, and / or wherein the DS OH Less than 2.7, or less than 2.6, or less than 2.5, less than 2.4, or less than 2.3, or less than 2.2, less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, or less than 1.5, or less than 1.4, or less than 1.3, or less than 1.2, or less than 1.1, or less than 1.0, or less than 0.

9.

12. The biodegradable microparticle according to any one of claims 1 to 11, wherein the mixed cellulose ester is cellulose acetate butyrate, or cellulose acetate butyrate, or a mixture thereof.

13. The biodegradable microparticle according to any one of claims 1 to 12, wherein the mixed cellulose ester is cellulose acetate butyrate.

14. The biodegradable microparticle according to any one of claims 1 to 13, wherein the biodegradable microparticle comprises at least 50 wt%, or at least 55 wt%, or at least 60 wt%, or at least 65 wt%, or at least 70 wt%, or at least 75 wt%, or at least 80 wt%, or at least 85 wt%, or at least 90 wt%, or at least 95 wt%, or at least 99 wt% of the mixed cellulose esters; and / or wherein the biodegradable microparticle comprises less than 99 wt%, or less than 95 wt%, or less than 90 wt%, or less than 85 wt%, or less than 80 wt%, or less than 75 wt%, or less than 70 wt% of the mixed cellulose esters.

15. The biodegradable microparticle of any one of claims 1-14, wherein the biodegradable microparticle consists essentially of the mixed cellulose esters.

16. The biodegradable microparticle according to any one of claims 1 to 15, wherein the biodegradable microparticle has at least 10%, or at least 20%, or at least 30%, or at least 40%, or at least 50%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95%, or at least 96%, or at least 97%, or at least 98%, or 20% to 100%, or 20% to 90%, or 20% to 80%, or 20% to 70%, or 20% to 60%, or 30% to 100%, or 30% to 90%, or 30% to 80%, or 30% to 70%, or 30% to 60%, or 40% to 100%. %, or 40% to 90%, or 40% to 80%, or 40% to 70%, or 40% to 60%, or 50% to 100%, or 50% to 90%, or 50% to 80%, or 50% to 70%, or 50% to 60%, or 60% to 100%, or 60% to 90%, or 60% to 80%, or 60% to 70%, or 70% to 100%, or 70% to 90%, or 70% to 80%, or 80% to 100%, or 80% to 90%, or 90% to 100% sphericity; and / or wherein the biodegradable microparticles have a sphericity of less than 100%, or less than 95%, or less than 90%, or less than 80%, or less than 70%, or less than 60%, or less than 50%.

17. The biodegradable microparticle according to any one of claims 1 to 16, wherein the biodegradable microparticle exhibits an oil absorption of at least 30 ml per 100 g, at least 35 ml per 100 g, or at least 40 ml per 100 g, or at least 45 ml per 100 g, or at least 50 ml per 100 g, or at least 55 ml per 100 g, or at least 60 ml per 100 g measured using test method ASTM D281, wherein mineral oil is used instead of castor oil.

18. A method for forming a biodegradable microparticle, the method comprising: (a) forming a coating comprising a mixed cellulose ester, wherein the mixed cellulose ester comprises- (i) an average degree of substitution ("DS") of acetyl substituents in the range of 0.1 to 2.3 Ac ”), (ii) an average degree of substitution ("DS") of propionyl substituents in the range of 0.1 to 1.5 Pr ”) or the average degree of substitution of butyryl substituents (“DS Bu "),as well as (iii) an average degree of substitution ("DS") of hydroxyl substituents in the range of 0.6 to 2.8 OH ”); (b) contacting at least a portion of the coating with an aqueous mixture under agitation to thereby form an initial emulsion; as well as (c) converting at least a portion of the initial emulsion into a dispersion comprising a solid phase and a liquid phase, wherein the solid phase comprises biodegradable microparticles; and (d) recovering at least a portion of the biodegradable microparticles from the dispersion, wherein the biodegradable microparticles exhibit a biodegradability of at least 50% at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods, wherein the biodegradable microparticles exhibit a haze transmittance of at least 10%.

19. The method of claim 18, wherein the biodegradable microparticles exhibit a haze transmittance of at least 15%, or at least 20%, or at least 25%, or at least 30%, or at least 35%, or at least 40%, or at least 45%, and / or wherein the biodegradable microparticles exhibit a haze transmittance of less than 90%, or less than 85%, or less than 80%, or less than 75%, or less than 70%, or less than 65%, or less than 60%, or less than 55%, or less than 50%, or less than 45%, or less than 40%, or less than 35%, or less than 32%, or less than 30%.

20. The method of any one of claims 18-19, wherein the biodegradable microparticles exhibit a span of at least 0.5, or at least 0.55, or at least 0.60, or at least 0.65, or at least 0.70, or at least 0.75, or at least 0.80, or at least 0.85, or at least 0.9, or at least 0.95, or at least 1.0, or at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2, or at least 1.25; and / or less than 3.0, or less than 2. .9, or less than 2.8, or less than 2.7, or less than 2.6, or less than 2.5, or less than 2.4, or less than 2.3, or less than 2.2, or less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, or from 1 to 2, or from 1 to 1.8, or from 1 to 1.6, or from 1.1 to 2, or from 1.1 to 1.8, or from 1.1 to 1.6, or from 1.2 to 2, or from 1.2 to 1.8, or from 1.2 to 1.6; and / or wherein the biodegradable microparticles have a mass fraction of 1 to 100, or 1 to 80, or 1 to 70, or 1 to 60, or 1 to 50, or 1 to 40, or 1 to 35, or 1 to 30, or 1 to 25, or 1 to 20, or 1 to 15, or 1 to 10, or 2 to 100, or 2 to 80, or 2 to 70, or 2 to 60, or 2 to 50, or 2 to 40, or 2 to 35, or 2 to 30, or 2 to 25, or 2 to 20, or 2 to 15, or 2 to 10, or 3 to 100, or 3 to 80, or 3 to 70, or 3 to 60, or 3 to 50, or 3 to 40, or 3 to 35, or 3 to 30, or 3 to 25, or 3 to 20, or 3 to 15, or 3 to 10, or 5 to 100, or 5 to 80, or 5 to 70, or 5 to 60, or 5 to 50, or 5 to 40, or 5 to 35, or 5 to 30, or 5 to 25, or 5 to 20, or 5 to 15, or 5 to 10, or 10 to 100, or 10 to 80 , or 10 to 70, or 10 to 60, or 10 to 50, or or 10 to 40, or 10 to 35, or 10 to 30, or 10 to 25, or 10 to 20, or 10 to 15, or 15 to 100, or 15 to 80, or 15 to 70, or 15 to 60, or 15 to 50, or 15 to 40, or 15 to 35, or 15 to 30, or 15 to 25, or 15 to 20, or 20 to 100, or 20 to 80, or 20 to 70, or Particle size based on D50 volume in a range of 20 to 60, or 20 to 50, or 20 to 40, or 20 to 35, or 20 to 30, or 25 to 100, or 25 to 80, or 25 to 70, or 25 to 60, or 25 to 50, or 25 to 40, or 25 to 35, or 25 to 30, or 30 to 100, or 30 to 80, or 30 to 70, or 30 to 60, or 30 to 50, or 30 to 40, or 30 to 35 microns.

21. The method of any one of claims 18-20, wherein the biodegradable microparticles exhibit at least 40%, or at least 45%, or at least 50%, or at least 55%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods, and / or wherein the mixed cellulose esters exhibit at least 40%, or at least 45%, or at least 50%, or at least 55%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95% biodegradability at 60 days according to at least one of the OECD 301B, OECD 301C, or OECD 301F test methods.

22. The method according to any one of claims 18-21, wherein the DS OH is at least 0.6, or at least 0.7, or at least 0.8, or at least 0.9, or at least 1.0, or at least 1.1, or at least 1.2, or at least 1.3, or at least 1.4, or from 0.5 to 0.95, or from 0.5 to 0.93, or from 0.5 to 0.91, or from 0.5 to 0.9, or from 0.5 to 0.85, or from 0.5 to 0.80, or from 0.5 to 0.75, or from 0.5 to 0.7, or from 0.55 to 0. 95, or 0.55 to 0.93, or 0.55 to 0.91, or 0.55 to 0.9, or 0.55 to 0.85, or 0.55 to 0.80, or 0.55 to 0.75, or 0.55 to 0.7, or 0.6 to 0.95, or 0.6 to 0.93, or 0.6 to 0.91, or 0.6 to 0.9, or 0.6 to 0.85, or 0.6 to 0.80, or 0.6 to 0.75, or 0.6 to 0.7, or 0.65 to 0.95, or 0.65 to 0.93, or 0.65 to 0.91, or 0.65 to 0.9, or 0.65 to 0.85, or 0.65 to 0.80, or 0.65 to 0.75, or 0.65 to 0.7, or 0.7 to 0.95, or 0.7 to 0.93, or 0.7 to 0.91, or 0.7 to 0.9, or 0.7 to 0.85, or 0.7 to 0.80, or 0.7 to 0.75, or 0.8 to 0.95, or 0.8 to 0.93, or 0.8 to 0.91, or 0.8 to 0.9, or 0.8 to 0.85, or 0.85 to 0.95, or 0.85 to 0.93, or 0.85 to 0.91, or 0.85 to 0.9, or 0.9 to 0.95, or 0.9 to 0.93, or 0.9 to 0.91; and / or wherein the DS OH Less than 2.7, or less than 2.6, or less than 2.5, or less than 2.4, or less than 2.3, or less than 2.2, or less than 2.1, or less than 2.0, or less than 1.9, or less than 1.8, or less than 1.7, or less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1.0, or less than 0.

9.

23. The biodegradable microparticle according to any one of claims 18 to 22, wherein the mixed cellulose ester is cellulose acetate butyrate.

24. The biodegradable microparticle according to any one of claims 18 to 23, wherein the biodegradable microparticle has at least 10%, or at least 20%, or at least 30%, or at least 40%, or at least 50%, or at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95%, or at least 96%, or at least 97%, or at least 98%, or 20% to 100%, or 20% to 90%, or 20% to 80%, or 20% to 70%, or 20% to 60%, or 30% to 100%, or 30% to 90%, or 30% to 80%, or 30% to 70%, or 30% to 60%, or 40% to 100%. %, or 40% to 90%, or 40% to 80%, or 40% to 70%, or 40% to 60%, or 50% to 100%, or 50% to 90%, or 50% to 80%, or 50% to 70%, or 50% to 60%, or 60% to 100%, or 60% to 90%, or 60% to 80%, or 60% to 70%, or 70% to 100%, or 70% to 90%, or 70% to 80%, or 80% to 100%, or 80% to 90%, or 90% to 100% sphericity; and / or wherein the biodegradable microparticles have a sphericity of less than 100%, or less than 95%, or less than 90%, or less than 80%, or less than 70%, or less than 60%, or less than 50%.

25. The method of any one of claims 18-24, wherein the biodegradable microparticles exhibit an oil absorption of at least 30 ml per 100 g, at least 35 ml per 100 g, at least 40 ml per 100 g, at least 45 ml per 100 g, at least 50 ml per 100 g, at least 55 ml per 100 g, or at least 60 ml per 100 g measured using test method ASTM D281, wherein mineral oil is used in place of castor oil.

26. A cosmetic composition comprising the biodegradable microparticles according to any one of claims 1 to 17.